Branched and hyperbranched ionomer polymers and uses thereof
Through the design and synthesis of branched ionomer polymers, the problem of poor performance of PFSA ionomers at high temperatures is solved, and the chemical and mechanical stability of hydrocarbon-based proton exchange membrane fuel cell is improved, and the ion resistance is reduced. Improves the overall performance of the fuel cell.
Patent Information
- Application Number
- CN202380032887.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-05
- Filing Date
- 2023-04-05
- Publication Date
- 2024-12-13
AI Technical Summary
Perfluorosulfonic acid (PFSA) ionomers used in existing hydrocarbon-based proton exchange membrane fuel cells (PEMFCs) have low chemical stability, complex production, high cost, potentially hazardous to the environment, and limited performance at high temperatures. It is difficult to meet the needs of thermochemical stability and economic feasibility.
Hyperbranched sulfonated phenylated poly(phenylene) is synthesized by Diels-Alder Addition reaction using branched ionomer polymers, including specific anionic comonomers and branched comonomers. Ionomers (HB-sPPT-H+) are used to improve chemical and mechanical stability and introduce proton conduction pathways into the catalyst layer to reduce ion resistance.
It is achieved to improve the performance of the fuel cell at high temperatures, reduce the ion resistance of the catalyst layer, improve the proton conductivity and catalyst activity, and enhance the stability and efficiency of the fuel cell.
Smart Images

Figure CN119137175A_ABST
Abstract
Description
[0001] CROSS REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of U.S. Provisional Application No. 63 / 327,479, filed on April 5, 2022, the contents of which are expressly incorporated herein by reference in their entirety. Background Art
[0003] Hydrocarbon-based ion exchange membranes (PEMs) and ionomers are intended for electrochemical applications such as fuel cells, electrolyzers, and water treatment due to their simple synthesis, low cost, low gas crossover, high T g Hydrocarbon-based ionomers are actively pursued as alternatives to conventional perfluorosulfonic acid (PFSA) ionomers due to their low thermal conductivity and less environmental concerns. Many different ion-containing polymers have been studied, with a focus on those containing aromatic groups in the polymer backbone, such as sulfonated derivatives of poly(arylene ether), poly(arylene ether ketone), poly(arylene sulfone), poly(imide), and poly(benzimidazole). However, hydrocarbon-based ionomers have so far generally been inhibited by a higher sensitivity to oxidative degradation either ex situ (e.g., Fenton's Reagent test) and / or in situ (e.g., in PEM fuel cells). Therefore, recent attention has focused on the rational design of hydrocarbon ionomers with enhanced chemical and mechanical stability.
[0004] Polyphenylenes, such as those reported by Stille and Müllen, have inherent chemical stability and mechanical strength. Sulfonated phenylated polyphenylenes (sPPP) are of particular interest as PEMs because of the inherent chemical and mechanical stability of the fully aromatic backbone. Sulfonated polyphenylenes are typically prepared by post-sulfonation of polyphenylenes and have recently been investigated for use in proton exchange membrane fuel cells (PEMFCs).
[0005] However, work in this area is limited by the challenge of synthesizing well-defined polymer backbones consisting of sterically hindered, rigid aryl-aryl linkages, with controlled sulfonation, and exhibiting high molecular weights. Another challenge includes limited solubility in polar solvents. Functionalization of polyphenylenes (e.g., sulfonation) results in irregular distribution of functional groups between monomer units and throughout the macroscopic polymer structure, thus producing structurally ill-defined polymers (see, e.g., Fujimoto CH; Hickner MA; Cornelius CJ; Loy DA Macromolecules 2005, 38, 5010).
[0006] Precise control of polymer structure and accurate placement of ionic functional groups along the polymer backbone can improve the short-range and long-range order of ion channels, thereby improving ionic conductivity. Polymer properties can be adjusted by controlling the introduction, placement and arrangement of sulfonic acid groups in the polymer. This arrangement is affected by the polymer backbone structure itself, which can be linear, branched, hyperbranched or have some other higher order structure. These polymer structures and their resulting properties affect the use of these polymers in end-use applications.
[0007] Hydrogen-related fuel cell technology is the goal of green and sustainable energy systems. Among the different types of fuel cells, proton exchange membrane fuel cells are considered to be economically viable, but the manufacturing and capital costs are still high. For example, the membrane electrode assembly (MEA) accounts for 50% of the capital cost of a PEMFC stack, of which >80% is related to the noble metal (PGM) catalyst used. Therefore, great efforts have been made to reduce the PGM content, although progress has been delayed due to the increase in mass transfer resistance, which depends largely on the morphology of the catalyst layer (CL).
[0008] Fuel cell catalyst layers are usually prepared from catalyst inks. In the catalyst inks, Pt-supported carbon catalyst particles aggregate into agglomerates, which aggregate into larger aggregates and form larger secondary pores. As described in the agglomerate model, these secondary pores facilitate the diffusion of gases and the transport of water within the CL. Polyelectrolytes (such as perfluorosulfonic acid (PFSA) ionomers, commonly referred to as trademarks) or ) can be included in the ink dispersion to encapsulate and bind the Pt / C aggregates, providing proton conduction pathways within the CL. The content and type of ionomer in the catalyst ink can greatly affect the mass transport resistance in the resulting CL.
[0009] There are significant disadvantages to using PFSA ionomers. Despite the extensive research surrounding PFSA ionomers, concerns are growing about the use of potentially hazardous chemical feedstocks. Additionally, the complex synthesis of PFSA ionomers limits production, as very few chemical manufacturing companies have the capability to produce these PFSA ionomers, driving up their expense. Furthermore, the 2030 goal of operating PEMFCs at high temperatures of 120°C may be limited by the relatively low thermal transition of PFSA at around 100°C.
[0010] To address the shortcomings of PFSA-based ionomers, thermochemically stable fluorine-free hydrocarbon ionomers are needed. Poor electrochemical kinetics, high ionic resistance and high mass transport resistance in the catalyst layer are the main parameters that lead to poor performance of proton exchange membrane fuel cells (PEMFCs) using hydrocarbon-based proton conducting ionomers. In addition, strategies for controlled synthesis of oligophenylenes and polymers are needed, which include controlling the introduction, position and frequency of anionic (e.g., sulfonated) functional groups in these fluorine-free hydrocarbon ionomers. The present disclosure attempts to meet these needs and provides additional advantages. Summary of the invention
[0011] This Summary is provided to introduce a selection of concepts in a simplified form that are further described below in the Detailed Description. This Summary is not intended to identify key features of the claimed subject matter, nor is it intended to be used as an aid in determining the scope of the claimed subject matter.
[0012] In one aspect, the present disclosure features branched ionomer polymers including anionic comonomers and branching comonomers. These branched ionomer polymers include repeating units of formula (I):
[0013]
[0014] in:
[0015] R 1A , R 1B , R 1C , R 1D , R 1E and R 1F is independently aryl or heteroaryl, each of which is optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cation, and the limiting condition is R 1A , R 1B , R 1C , R 1D , R 1E and R 1F At least two of them are independently selected from SO3 by 1, 2, 3, 4 or 5 independently selected - X + PO3 2- X + 2 and COO - X +A substituent substituted aryl or heteroaryl, wherein X + Yes H + or cations;
[0016] R 1G and R 1H is independently H, aryl or heteroaryl, wherein the aryl and heteroaryl are each optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cations;
[0017] A1 is arylene, heteroarylene, aralkylene or heteroaralkylene, each of which is optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl; and
[0018] A2 is absent, arylene or heteroarylene, wherein said arylene and heteroarylene are each optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl;
[0019] B is a branched comonomer;
[0020] R 2A is the key; and
[0021] The first repeating unit of formula (I) is 2A The second repeating unit of formula (I) is combined to form a branched structure.
[0022] The branched comonomer (B) may comprise formula (II):
[0023]
[0024] in:
[0025] L3 at each occurrence is optionally substituted with 1, 2 or 3 independently selected from C 1-6 Substitution of alkyl, halo, nitro, cyano, aryl and heteroaryl substituents;
[0026] L2 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C1-6 Alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; and
[0027] L1 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 Substituents of alkyl, halo, nitro, cyano, aryl and heteroaryl groups are substituted.
[0028]
[0013] The present disclosure also features a method of making the branched ionomer polymers of the present disclosure.
[0029] In another aspect, the disclosure features a catalyst ink formulation including the branched ionomer polymer of the disclosure.
[0030] In another aspect, the disclosure features an ionic polymer membrane including the branched ionomer polymer of the disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above-mentioned aspects of the present invention and many of the attendant advantages will become more readily understood as the following detailed description is better understood with reference to the accompanying drawings, in which:
[0032] Figure 1A Display HB-sPPT-H + 3D illustration of the chemical structure of
[0033] Figure 1B Display HB-sPPT-H + (a hyperbranched ionomer polymer) which can be observed through an optical microscope equipped with a UV filter before mechanical grinding,
[0034] Figure 1C Display HB-sPPT-H + An example of which can be observed through an optical microscope equipped with a UV filter after mechanical grinding;
[0035] Figure 1D Display HB-sPPT-H + and linear sPPB-H + Water absorption properties of polymers measured at 80±0.5℃;
[0036] Figure 1E Display HB-sPPT-H + images in water;
[0037] Figure 1F The results show that the hyperbranched sulfonated, phenylated poly(phenylene) terphenyl (HB-sPPT-H) can be used as a catalyst layer binder. + )'s chemical structure;
[0038] Figure 2A The use of 15 wt% linear sPPB-H + , 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + , 7.5 wt% HB-sPPT-H + +7.5 wt% linear sPPB-H + and 10 wt% HB-sPPT-H + +5 wt% linear sPPB-H + Polarization and power curves of a CCM prepared with a catalyst layer of wherein the data were obtained at 80°C, 100% RH and 1 atm pressure under H2 / O2 operation; and
[0039] Figure 2B The use of 15 wt% linear sPPB-H + , 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + , 7.5 wt% HB-sPPT-H + +7.5 wt% linear sPPB-H + and 10 wt% HB-sPPT-H + +5 wt% linear sPPB-H + Polarization and power curves of CCMs prepared with a catalyst layer of . Data were obtained at 80 °C, 100% RH, 1 atm pressure, H2 / air operation and 35 ± 5 μm (sPPB-H + ) film thickness;
[0040] Figure 3A Display use includes 30 wt% 25 wt% HB + 5 wt% 20 wt% HB + 10 wt% 15 wt% HB + 15 wt% 10 wt% HB + 20 wt% and 5 wt% HB + 25 wt% Polarization and power curves of CCM prepared with catalyst layer, where the data were obtained at 80°C, 100% RH, 1atm pressure and H2 / O2 operation;
[0041] Figure 3B Display use includes 30 wt% 25 wt% HB + 5 wt% 20 wt% HB + 10 wt% 15 wt% HB + 15 wt% 10 wt% HB + 20 wt% and 5 wt% HB + 25 wt% Polarization and power curves of CCMs prepared with catalyst layers of , where the data were operated at 80 ° C, 100% RH, 1 atm pressure, H2 / air and 25 ± 5 μm ( NR-211) film thickness;
[0042] Figure 4A Display uses include linear sPPB-H + 、5 wt% HB + 10 wt% linear sPPB-H + and 10 wt% linear sPPB-H + The CCM prepared with the catalyst layer was operated at 80 °C, 100% RH, 1 atm pressure and 33 ± 5 μm (sPPB-H + ) Polarization and power curves obtained at film thickness;
[0043] Figure 4B Display uses include linear sPPB-H + 、5 wt% HB + 10 wt% linear sPPB-H + and 10 wt% linear sPPB-H + The CCM prepared with the catalyst layer was operated in H2 / air at 80°C, 100% RH, 1 atm pressure and 33 ± 5 μm (sPPB-H + ) Polarization and power curves obtained at film thickness;
[0044] Figure 4C The results show that the sPPB-H + ) Tafel relation obtained for the film thickness, where the inset shows the linearized region where the Tafel equation is valid;
[0045] Figure 4D The results show that the sPPB-H + ) Nyquist plot at 0.8 V and 0.5 slpm H2 / 1.0 slpm O2 obtained at film thickness;
[0046] Figure 4E Displayed catalyst loading: 0.4 mg Pt cm -2 , 0.5slpm H2 / 0slpm N2, scan rate: 50mV s -1 , at 80°C, 100% RH, 1atm pressure and 33±5μm (sPPB-H +) CV scans obtained at film thickness;
[0047] Figure 4F Nyquist plots at 0.5 slpm H2 / 0.5 slpm N2 are shown, with the inset showing the peaks at 80°C, 100% RH, 1 atm pressure and 33 ± 5 μm (sPPB-H + ) Extension of the high frequency region obtained under the film thickness;
[0048] Figure 5A Display use includes 30 wt% 5 wt% HB-sPPT-H + +25% by weight and 25 wt% The CCM prepared with the catalyst layer was operated at 80 °C, 100% RH, 1 atm pressure and 25 ± 5 μm ( Polarization and power curves obtained at film thickness NR-N211);
[0049] Figure 5B Display use includes 30 wt% 5 wt% HB-sPPT-H + +25% by weight and 25 wt% The CCM prepared with the catalyst layer was operated in H2 / air at 80°C, 100% RH, 1 atm pressure and 25 ± 5 μm ( Polarization and power curves obtained at film thickness NR-N211);
[0050] Figure 5C Displayed at 80°C, 100% RH, 1atm pressure and 25±5μm ( NR-N211) Tafel relation obtained for the film thickness, where the inset shows the linearization region in which the Tafel equation is valid;
[0051] Figure 5D Displayed at 80°C, 100% RH, 1atm pressure and 25±5μm ( Nyquist plot at 0.8 V and 0.5 slpm H2 / 1.0 slpm O2 obtained at film thickness NR-N211);
[0052] Figure 5E Displayed catalyst loading: 0.4 mg Pt / cm 2 , 0.5slpm H2 / 0slpm N2, scan rate: 50mV s -1 , at 80°C, 100% RH, 1atm pressure and 25±5μm( CV scans obtained at NR-N211) film thickness;
[0053] Fig. 5F Nyquist plots at 0.5 slpm H2 / 0.5 slpm N2 are shown, with the inset showing the pressure at 80°C, 100% RH, 1 atm pressure and 25 ± 5 μm ( NR-N211) expansion of the high-frequency region obtained at the film thickness;
[0054] Fig. 6A The use of 15 wt% linear sPPB-H + (CCM 1), 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + (CCM 2), 30 wt% (CCM 3) and 5 wt% HB-sPPT-H + +25% by weight Polarization and power curves of the prepared CCMs under H2 / O2 operation and constant 1 slpm flow rate at 80 °C, 100% RH, 1 atm pressure. Membrane thickness: 33 ± 5 μm for CCM 1 and CCM 2 (sPPB-H + ); CCM 3 and CCM 4 are 25±5μm ( NR-N211);
[0055] Figure 6B The use of 15 wt% linear sPPB-H + (CCM 1), 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + (CCM 2), 30 wt% (CCM 3) and 5 wt% HB-sPPT-H + +25% by weight Polarization and power curves of the prepared CCMs under H2 / air operation and constant 1 slpm flow rate at 80 °C, 100% RH, 1 atm pressure. Membrane thickness: 33 ± 5 μm for CCM 1 and CCM 2 (sPPB-H + ); CCM 3 and CCM 4 are 25±5μm ( NR-N211);
[0056] Figure 6CThe Tafel relationship obtained at 80°C, 100% RH, 1 atm pressure is shown, and the inset shows the linearization region where the Tafel equation is valid. Membrane thickness: 33 ± 5 μm for CCM 1 and CCM 2 (sPPB-H + ); CCM 3 and CCM 4 are 25±5μm ( NR-N211);
[0057] Fig.6D Nyquist plots at 0.8 V and 0.5 slpm H2 / 1.0 slpm O2 obtained at 80°C, 100% RH, 1 atm pressure are shown. Film thickness: 33 ± 5 μm for CCM 1 and CCM 2 (sPPB-H + ); Film thickness: 25±5μm for CCM 3 and CCM 4 ( NR-N211);
[0058] Fig. 6E Displayed catalyst loading: 0.4 mg Pt cm -2 , 0.5slpm H2 / 0slpm N2, scan rate: 50mV s -1 , CV scans obtained at 80°C, 100% RH, 1 atm pressure. Film thickness: 33 ± 5 μm for CCM 1 and CCM 2 (sPPB-H + ); CCM 3 and CCM 4 are 25±5μm ( NR-N211);
[0059] Fig. 6F Nyquist plots at 0.5 slpm H2 / 0.5 slpm N2 are shown, with the inset showing the expansion of the high frequency region obtained at 80°C, 100% RH, 1 atm pressure. Film thickness: 33 ± 5 μm for CCM 1 and CCM 2 (sPPB-H + ); CCM 3 and CCM 4 are 25±5μm ( NR-N211);
[0060] Fig. 7A 15 wt% linear sPPB-H is shown + Cross-sectional SEM of ionomer (CCM 1);
[0061] Figure 7B 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + (CCM 2) cross-sectional SEM;
[0062] Figure 7C Display 30 wt% Cross-sectional SEM of ionomer (CCM 3);
[0063] Fig.7D 5 wt% HB-sPPT-H + +25% by weight (CCM 4) cross-sectional SEM;
[0064] Fig. 7E Shows the N2 adsorption isotherms (converted to STP and relative to carbon mass) for the comparative CCMs, V ads Cross-sectional SEM for relative pressure / saturation pressure (P / P0);
[0065] Figure 7F Cross-sectional SEM showing the pore size distribution determined from the adsorption isotherm;
[0066] Figure 8 shows a t-diagram from which the micropore volume (<2 nm pores) and mesopore + macropore volume (2 to 50 nm + >50 nm) are determined;
[0067] Fig.9A It shows that there is Schematic diagram of the catalyst layer structure;
[0068] Fig. 9B The presence of linear sPPB-H in PEMFC CL + Schematic diagram of the catalyst layer structure of the ionomer;
[0069] Fig. 9C The presence of HB-sPPT-H in PEMFC CL + Schematic diagram of the catalyst layer structure of the particle;
[0070] Fig.10 The results show that the hyperbranched sulfonated phenylated poly(phenylene) homopolymer (HB-sPPT-H + )'s synthetic route;
[0071] Fig.11A SEM micrographs are shown showing 5 wt% HB-sPPT-H at 1000x magnification. + + 10 wt% linear sPPB-H + Surface roughness;
[0072] Fig. 11B SEM micrographs are shown showing 7.5 wt% HB-sPPT-H at 1000x magnification. + +7.5 wt% linear sPPB-H + Surface roughness;
[0073] Fig. 11CSEM micrographs are shown showing 10 wt % HB-sPPT-H at 1000x magnification. + +5 wt% linear sPPB-H + Surface roughness;
[0074] Fig.11D SEM micrographs are shown showing the formation of 5 wt% HB-sPPT-H at 1000x magnification. + + 10 wt% linear sPPB-H + the thickness of the prepared catalyst coating film;
[0075] Fig.11E SEM micrographs are shown showing the presence of 7.5 wt% HB-sPPT-H at 1000x magnification. + +7.5 wt% linear sPPB-H + the thickness of the prepared catalyst coating film;
[0076] Fig.11F SEM micrographs are shown showing the formation of 10 wt% HB-sPPT-H + +5 wt% linear sPPB-H + the thickness of the prepared catalyst coating film;
[0077] Fig. 12A It is shown that 15 wt% sPPB-H + , 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + and 10 wt% sPPB-H + Plots of mass activity and specific activity obtained for the fabricated CCM at 80 °C, 100% RH, and 1 atm pressure;
[0078] Fig. 12B Shown by 30 wt% 5 wt% HB-sPPT-H + +25% by weight and 30 wt% Plots of mass activity and specific activity obtained for the fabricated CCM at 80 °C, 100% RH, and 1 atm pressure;
[0079] Fig.13A The performance graph of the MEA is shown, which shows that the Pt catalyst loading on the anode and cathode is 0.4 mgPt / cm2 under H2 / O2. 2 , and the operating conditions are polarization and power curves at 80°C, 100% RH and 1 atm pressure; and
[0080] Fig. 13BPerformance graph of the MEA is shown, which indicates a Pt catalyst loading of 0.4 mg Pt / cm on the anode and cathode under H2 / air operation. 2 , and the operating conditions are polarization and power curves under 80°C, 100% RH and 1atm pressure. DETAILED DESCRIPTION
[0081] It will be appreciated that, although specific embodiments of the disclosure have been described herein for purposes of illustration, various modifications may be made without deviating from the spirit and scope of the disclosure.
[0082] Sulfonated poly(arylene ether) and sulfophenylated polyphenylene ionomers can exhibit improved chemical stability relative to PFSA. In one illustrative example, biphenyl comonomer (sPPB-H + ) provides improved stability at the expense of reduced ionic conductivity.
[0083] Furthermore, molecular branching of ionomer polymers is explored to reduce dimensional expansion and improve mechanical integrity of such hydrocarbon ionomers when cast as PEMs. Notably, as the water absorption of the branched ionomer polymers described herein decreases, their electrical conductivity increases.
[0084] Herein, non-size-expandable, non-conformal, hyperbranched sulfonated poly(phenylene) ionomer particles (HB-sPPT- + ) introduces a direct pathway for proton conduction in the hydrocarbon ionomer-based catalyst layer (CL).
[0085] definition
[0086] At various places in this specification, substituents of compounds of the present disclosure are disclosed in groups or ranges. It is specifically intended that the present disclosure encompass every individual subcombination of the members of these groups and ranges. For example, the term "C1-6 alkyl" is specifically intended to individually disclose methyl, ethyl, C3 alkyl, C4 alkyl, C5 alkyl, and C6 alkyl. For example, the term "optionally substituted with 1, 2, 3, 4, or 5 ... " is intended to individually disclose optional substitution with 1, 2, 3, or 4; 1, 2, or 3; 1 or 2; or 1 substituent.
[0087] It is further desirable that the compounds of the present disclosure are stable. As used herein, "stable" refers to a compound that is sufficiently robust to survive isolation to a useful degree of purity from a reaction mixture.
[0088] It should be further understood that certain features of the present disclosure described for clarity in the context of separate embodiments may also be provided in combination in a single embodiment. Conversely, various features of the present disclosure described for brevity in the context of a single embodiment may also be provided separately or in any suitable sub-combination.
[0089] Unless explicitly described, it is contemplated that a divalent group, such as a linking group between the first and second moieties (eg, alkylene, arylene, etc.) may be oriented in both forward and reverse directions relative to the first and second moieties.
[0090] An "optionally substituted" group may refer to a functional group that may be substituted or unsubstituted, for example, with another functional group. For example, when a group is unsubstituted, it may be referred to by its group name, such as alkyl or aryl. When a group is substituted with another functional group, it may be more generally referred to as a substituted alkyl or substituted aryl.
[0091] As used herein, the term "substituted" or "substitution" refers to the replacement of a hydrogen atom with a substituent other than H. For example, "N-substituted piperidin-4-yl" refers to the replacement of the H atom from the NH of the piperidinyl group with a non-hydrogen substituent such as, for example, an alkyl group.
[0092] As used herein, the term "about" may be understood to include values within 10% of the stated value.
[0093] As used herein, the term "alkyl" refers to a straight or branched hydrocarbon group. In some embodiments, the alkyl group has 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms, 1 to 3 carbon atoms, 1 to 2 carbon atoms, or 1 carbon atom. Representative alkyl groups include methyl, ethyl, propyl (e.g., n-propyl, isopropyl), butyl (e.g., n-butyl, sec-butyl and tert-butyl), pentyl (e.g., n-pentyl, tert-pentyl, neopentyl, isopentyl, penta-2-yl, penta-3-yl) and hexyl (e.g., n-hexyl and isomers) groups.
[0094] As used herein, the term "alkylene" refers to a linked alkyl group.
[0095] As used herein, the term "cycloalkyl" refers to a non-aromatic carbocyclic ring, which includes cyclized alkyl, alkenyl and alkynyl. Cycloalkyl may include a monocyclic or polycyclic (e.g., with 2, 3 or 4 fused rings) ring system (including spirocycle). In certain embodiments, cycloalkyl may have 3 to about 20 carbon atoms, 3 to about 14 carbon atoms, 3 to about 10 carbon atoms or 3 to 7 carbon atoms. Cycloalkyl may further have 0, 1, 2 or 3 double bonds and / or 0, 1 or 2 triple bonds. The definition of cycloalkyl also includes a portion of an aromatic ring having one or more fused (that is, with a common bond) with a cycloalkyl ring, such as benzo derivatives of pentane, pentene, hexane, etc. Cycloalkyl with one or more fused aromatic rings may be connected by an aromatic or non-aromatic moiety. One or more annular carbon atoms of cycloalkyl may, for example, be oxidized by having a pendant oxygen group or a sulfide ion group (sulfido) substituent. Examples of cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclopentenyl, cyclohexenyl, cyclohexadienyl, cycloheptatrienyl, norbornyl, norpinyl, norcamyl, adamantyl, and the like.
[0096] As used herein, the term "cycloalkylene" refers to a linked cycloalkyl group.
[0097] As used herein, the term "perfluoroalkyl" refers to a linear or branched fluorocarbon chain. In some embodiments, the perfluoroalkyl has 1 to 10 carbon atoms (e.g., 1 to 8 carbon atoms, 1 to 6 carbon atoms, 1 to 3 carbon atoms, 1 or 2 carbon atoms, or 1 carbon atom). Representative alkyls include trifluoromethyl, pentafluoroethyl, etc.
[0098] As used herein, the term "perfluoroalkylene" refers to a linked perfluoroalkyl group.
[0099] As used herein, the term "heteroalkyl" refers to a linear or branched alkyl group, and one or more carbon atoms are replaced with a heteroatom selected from O, N, or S. In some embodiments, the heteroalkyl group has 1 to 10 carbon atoms (e.g., 1 to 8 carbon atoms, 1 to 6 carbon atoms, 1 to 3 carbon atoms, 1 or 2 carbon atoms, or 1 carbon atom).
[0100] As used herein, the term "heteroalkylene" refers to a linked heteroalkyl group.
[0101] As used herein, the term "alkoxy" refers to an alkyl or cycloalkyl group as described herein bonded to an oxygen atom. In some embodiments, the alkoxy group has 1 to 10 carbon atoms (e.g., 1 to 8 carbon atoms, 1 to 6 carbon atoms, 1 to 3 carbon atoms, 1 or 2 carbon atoms, or 1 carbon atom). Representative alkoxy groups include methoxy, ethoxy, propoxy, and isopropoxy.
[0102] As used herein, the term "perfluoroalkoxy" refers to a perfluoroalkyl or cyclic perfluoroalkyl group as described herein bonded to an oxygen atom. In some embodiments, the perfluoroalkoxy group has 1 to 10 carbon atoms (e.g., 1 to 8 carbon atoms, 1 to 6 carbon atoms, 1 to 3 carbon atoms, 1 or 2 carbon atoms, or 1 carbon atom). Representative perfluoroalkoxy groups include trifluoromethoxy, pentafluoroethoxy, and the like.
[0103] As used herein, the term "aryl" refers to an aromatic hydrocarbon group having 6 to 10 carbon atoms. Representative aryl groups include phenyl. In some embodiments, the term "aryl" includes aromatic hydrocarbons of monocyclic or polycyclic (e.g., having 2, 3 or 4 condensed rings), such as, for example, phenyl, naphthyl, anthracenyl, phenanthrenyl, dihydroindenyl and indenyl.
[0104] As used herein, the term "arylene" refers to a linked aryl group. For example, the term "phenylene" refers to a linked phenyl group.
[0105] As used herein, the term "aralkyl" refers to an alkyl or cycloalkyl group as defined herein in which one of the alkyl hydrogen atoms is replaced with an aryl group as defined herein. A representative aralkyl group is benzyl.
[0106] As used herein, the term "aralkylene" refers to a linked aralkyl group.
[0107] As used herein, the term "heteroaryl" refers to a 5- to 10-membered aromatic monocyclic or bicyclic ring containing 1 to 4 heteroatoms selected from O, S and N. Representative 5- or 6-membered aromatic monocyclic ring groups include pyridine, pyrimidine, pyridazine, furan, thiophene, thiazole, oxazole and isoxazole. Representative 9- or 10-membered aromatic bicyclic ring groups include benzofuran, benzothiophene, indole, pyranopyrrole, benzopyran, quinoline, benzocyclohexyl and naphthyridine.
[0108] As used herein, the term "heteroarylene" refers to a linked heteroaryl group.
[0109] As used herein, the term "heteroaralkyl" refers to an alkyl or cycloalkyl group as defined herein in which one of the alkyl hydrogen atoms is replaced with an aryl or heteroaryl group as defined herein. For example, a representative aralkyl group is benzyl.
[0110] As used herein, the term "heteroaralkylene" refers to a linked heteroaralkyl group.
[0111] As used herein, the term "halogen" or "halo" refers to fluoro, chloro, bromo, and iodo groups.
[0112] As used herein, the term "copolymer" refers to a polymer formed by polymerization of two or more different monomers. The number and properties of each constituent unit in the copolymer can be controlled individually. Unless otherwise expressly stated, the constituent units can be configured in a completely random, alternating random, regular alternating, regular block or random block configuration. A completely random configuration may be, for example, x xy zxyyzyzz z ... or yzxyzyzx x .... An alternating random configuration may be: xyxzyxy zy x z ..., and a regular alternating configuration may be, for example, xyzxyzxy z .... A regular block configuration (that is, a block copolymer) has the following general configuration: ...xxxyyyzzzxx x ..., while a random block configuration has the following general configuration, for example: ...xxxzzxxyyyyzzzxxzz z ..., or for example ...xxxyyyyxxyyyxxxyy ....
[0113] As used herein, the term "constituent unit" of a polymer refers to an atom or group of atoms in a polymer, including a portion of the chain together with its side atoms or groups of atoms (if any). A constituent unit may be a repeating unit. A constituent unit may also refer to an end group on a polymer chain. For example, a constituent unit of polyethylene glycol may be -CH2CH2O- corresponding to a repeating unit, or -CH2CH2OH corresponding to an end group.
[0114] As used herein, the term "repeating unit" corresponds to the smallest constituent unit, which is repeated to constitute a macromolecule (or oligomer molecule or block).
[0115] As used herein, the term "end group" refers to a constituent unit located at the end of a polymer and having only one connection to the polymer chain. For example, the end group may be derived from a monomer unit at the end of the polymer once the monomer unit is polymerized. As another example, the end group may be part of a chain transfer agent or initiator used to synthesize the polymer.
[0116] As used herein, the term "terminal" of a polymer refers to a constituent unit of the polymer located at the terminal of the main chain of the polymer.
[0117] As used herein, the term "terminal group" refers to a functional group located at the end of a polymer backbone chain.
[0118] As used herein, the term "cationic" refers to a moiety that is positively charged or ionizable under physiological conditions to a positively charged moiety. Examples of cationic moieties include, for example, amine, ammonium, pyridinium, imine, sulfonium, quaternary phosphonium groups, and the like.
[0119] As used herein, the term "anionic" refers to a functional group that is negatively charged or can be ionized into a negatively charged moiety under physiological conditions. Examples of anionic groups include carboxylates, sulfates, sulfonates, phosphates, and the like.
[0120] As used herein, the term "branched" refers to a polymer comprising side chains or "branches" growing from a main polymer segment (e.g., a polymer backbone). The branches are composed of the same repeating units as the main segment. Branched ionomer polymers include relatively low abundance branching comonomers in the ionomer polymer relative to hyperbranched ionomer polymers, which have a higher abundance of branching comonomers in the ionomer polymer. Branched ionomer polymers may comprise a mixture of linear and branched segments.
[0121] As used herein, the term "hyperbranching" refers to a polymer comprising a three-dimensional polymer structure different from a regular dendritic structure, and it may include a mixture of straight chain and branched segments. The hyperbranched ionomer polymer includes a relatively high abundance of branched comonomers in the ionomer polymer than that present in the branched ionomer polymer. For example, the polymer composition may include between about 20 mol% and about 40 mol%, between about 20 mol% and about 30 mol%, between about 20 mol% and about 25 mol%, between about 18 mol% and about 22 mol%, or about 20 mol% of branched monomers. The hyperbranched ionomer polymer typically contains little or no straight chain segments. The hyperbranched ionomer polymer described herein may be represented as HB-sPPT-H + .
[0122] Branched and hyperbranched ionomeric polymers are distinguished from crosslinked polymers in that branched or hyperbranched ionomeric polymers contain no linkages between polymer chains or pre-existing polymer chains.
[0123] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art are generally understood. Although methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present disclosure, suitable methods and materials are described as follows. All publications, patent applications, patents and other references mentioned herein are incorporated by reference in their entirety. In the event of a conflict, this specification (including definitions) shall prevail. In addition, the materials, methods and examples are illustrative only and are not intended to be limiting.
[0124] Branched ionomer polymers and hyperbranched ionomer polymers
[0125] The polymers disclosed herein may be branched and / or hyperbranched. Without wishing to be bound by theory, in some embodiments, branched and / or hyperbranched ionomer polymers may have improved properties compared to their linear polymer analogs. Branched and / or hyperbranched ionomer polymers may include branched comonomers (B), and they are covalently bound to at least three anionic comonomer units. Branched and / or hyperbranched ionomer polymers may be synthesized by reacting functionalized branched comonomers (e.g., dienophiles) having three or more reactive functional groups with functionalized anionic comonomers (e.g., dienes) having two or more diene functional groups. This composition can be branched by dienophilic comonomers. In addition, branched and / or hyperbranched ionomer polymers can be synthesized by reacting a functionalized anionic comonomer (e.g., a diene) having three or more reactive diene functional groups with a dienophilic comonomer (e.g., an alkyne and / or ketone) having two or more functional groups. This composition can be branched by a diene comonomer. In addition, branched and / or hyperbranched ionomer polymers can be synthesized by reacting a functionalized anionic comonomer (e.g., a diene) having three or more reactive diene functional groups with a dienophilic comonomer (e.g., an alkyne and / or ketone) having three or more functional groups. This composition can be branched by a diene comonomer and a dienophilic comonomer. Examples of branched dienophilic comonomers and branched dienes include, but are not limited to, 3, 4, 5, and / or 6-directional functional groups. Scheme 1 depicts a branched ionomer polymer comprising a trifunctional branched dienophilic monomer.
[0126] The polyvalent linker (that is, comonomer) can be incorporated into the polymer using a polyfunctional aromatic system terminated by an alkyne or protected alkyne, and then used to react with a dienophilic comonomer to create a branch point according to Schemes 1 and 2. The diene comonomer can be a mixture of anionic comonomers and hydrophobic uncharged comonomers. The functionalized branched aromatic system can be small, such as 1,3,5-triethynylbenzene, or larger, with more than one aromatic group.
[0127] Solution 1 : Synthesis of an exemplary sulfonated, phenylated polyphenylene ionomer branched ionomer polymer and comprising a trifunctional monomer B to induce branching between linear segments of a difunctional anionic monomer A and a difunctional monomer C.
[0128]
[0129] Solution 2 :Hyperbranched ionomer polymer (HB-sPPT-H +) and include a trifunctional monomer B to achieve branching, with little or no linear segment of the synthesis of exemplary sulfonated, phenylated polyphenylene ionomers. Scheme 2 can completely omit the difunctional monomer C (shown), or can include a difunctional monomer C.
[0130]
[0131] The polymers of the present disclosure include branched ionomeric polymers comprising repeating units of formula (I):
[0132]
[0133] in:
[0134] R 1A , R 1B , R 1C , R 1D , R 1E and R 1F is independently aryl or heteroaryl, each of which is optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cation, and the limiting condition is R 1A , R 1B , R 1C , R 1D , R 1E and R 1F At least two of them are independently selected from SO3 by 1, 2, 3, 4 or 5 independently selected - X + PO3 2- X + 2 and COO - X + A substituent substituted aryl or heteroaryl, wherein X + Yes H + or cations;
[0135] R 1G and R 1H is independently H, aryl or heteroaryl, wherein the aryl and heteroaryl are each optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X+ 2 and COO - X + Substituents, where X + Yes H + or cations;
[0136] A1 is arylene, heteroarylene, aralkylene or heteroaralkylene, each of which is optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl; and
[0137] A2 is absent, arylene or heteroarylene, wherein said arylene and heteroarylene are each optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl;
[0138] B is a branched comonomer;
[0139] R 2A is a key; and
[0140] The first repeating unit of formula (I) is 2A The second repeating unit of formula (I) is combined to form a branched structure.
[0141] The branched ionomer polymer comprising repeating units of formula (I) may comprise anionic comonomer units and branching comonomer (B) units.
[0142] In some embodiments, the anionic comonomer includes more than one aromatic group, more than 6 aromatic groups, less than 10 aromatic groups, exactly 7 aromatic groups, or exactly 9 aromatic groups, and further includes more than one anionic substituent (e.g., sulfonate, phosphonate, and / or carboxylate), between 2 and 7 anionic substituents, between 2 and 6 anionic substituents, between 2 and 4 anionic substituents, between 4 and 10 anionic substituents, at least 2 anionic substituents, or 4 or fewer anionic substituents.
[0143] Anionic substituents may include one or more groups, which are the same or different, and which are anionic at physiological pH, or are neutral at physiological pH but become anionic when the pH is greater than the pKa of the substituent. For example, the anionic group may include sulfonate, phosphonate, carboxylate, or a combination thereof.
[0144] Each anionic substituent (e.g., sulfonate, phosphonate, and / or carboxylate) can be protonated or have a non-protonated counter ion. + is a counter ion and can be H + , cations, alkali metal ions (such as Li + 、Na + , K + , Rb+ and / or Cs + ), ammonium, substituted ammonium (such as alkyl, aryl or heteroaryl substituted ammonium), or a combination thereof. For example, ammonium can be [N(R 5A )(R 5B )(R 5C )(R 5D )] + , where R 5A , R 5B , R 5C and R 5D Independently H, C 1-6 Alkyl, aryl, aralkyl or heteroaryl.
[0145] In a representative embodiment, the anionic comonomer unit comprises a structure according to formula (VII):
[0146]
[0147] In some embodiments, the branched comonomer (B) unit comprises a structure of formula (II):
[0148]
[0149] in:
[0150] L3 at each occurrence is optionally substituted with 1, 2 or 3 independently selected from C 1-6 Substitution of alkyl, halo, nitro, cyano, aryl and heteroaryl substituents;
[0151] L2 is absent, arylene or heteroarylene, wherein each of the arylene and heteroarylene groups is optionally substituted by 1, 2, 3 or 4 groups independently selected from C 1-6 Alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; and
[0152] L1 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 Substituents of alkyl, halo, nitro, cyano, aryl and heteroaryl groups are substituted.
[0153] In an illustrative example, the branched comonomer (B) may include a structure of formula (III):
[0154]
[0155] The branched ionomeric polymer comprising repeating units of formula (I) may comprise anionic comonomer units having a frequency "Y" and branching comonomer (B) units having a frequency "Z".
[0156] In some embodiments, the molar ratio of Z:Y in the polymer is from about 1:3 to about 1:2, from about 1:4 to about 2:3, from about 1:5 to about 3:4, about 1:2, or about 1:3.
[0157] The relative molar composition of Z:Y can affect the degree of branching and the structural, material, and electronic properties of the resulting polymer. Thus, for values of molar ratios less than about 1:3 or greater than about 1:2, or less than about 1:3 or greater than about 2:3, or less than about 1:4 or greater than about 1:2, the degree of branching may be too low or too high, respectively, for the polymer to exhibit the desired ionomeric properties, as described in Examples 1 to 4 below.
[0158] As described herein, the anionic comonomer and the branching comonomer (B) are linked by a covalent bond.
[0159] In one embodiment, the repeating unit comprises a structure of formula (IV):
[0160]
[0161] In some embodiments, the polymer is insoluble in polar solvents. Polar solvents may include water, alcohols (e.g., methanol, ethanol, propanol, isopropanol, n-butanol, and / or tert-butanol). In some embodiments, the polymer is insoluble in low boiling alcohols. Low boiling points include boiling points below about 120°C, below about 100°C, below about 90°C, below about 85°C, below about 80°C, below about 70°C, between about 60°C and about 80°C, between about 60°C and about 85°C, or between about 60°C and about 120°C, examples of low boiling alcohols include methanol, ethanol, propanol, isopropanol, n-butanol, tert-butanol, etc.
[0162] In some embodiments, the polar solvent comprises an alcohol, water, or a combination thereof. In some embodiments, the polar solvent comprises a combination of more than one component, such as an alcohol and water or a combination of more than one different alcohol and water. In embodiments where the polar solvent comprises an alcohol and water, the composition of the polar solvent may be about 1:1 volume to volume ratio of water to alcohol, about 1:2 volume to volume ratio of water to alcohol, about 1:3 volume to volume ratio of water to alcohol, about 1:4 volume to volume ratio of water to alcohol, about 1:2.5 volume to volume ratio of water to alcohol, or about 1:3.5 volume to volume ratio of water to alcohol.
[0163] The branched ionomer polymer of formula (I) can be formed by polymerizing a functionalized branched comonomer (B) with a functionalized anionic comonomer. The polymerization may include reacting Z in a Diels-Alder addition reaction. m Molar ratio of functionalized comonomer (B) to Y m moles of functionalized anionic comonomers are polymerized.
[0164] In polymer synthesis, the functionalized branched comonomer (B) is a dienophile and may include more than one alkyne functional group, two or more alkyne functional groups, three or more alkyne functional groups, between two and four alkyne functional groups, between two and six alkyne functional groups, exactly six alkyne functional groups, exactly five alkyne functional groups, exactly four alkyne functional groups, or exactly three alkyne functional groups. For example, the functionalized branched comonomer (B) may be a trifunctional comonomer (B) including three alkyne functional groups.
[0165] In polymer synthesis, the functionalized anionic comonomer is a diene. The functionalized anionic comonomer may include one diene, two dienes, three dienes, or four dienes in the functionalized anionic comonomer reagent.
[0166] The molar ratio of the functionalized branched comonomer (B) to the functionalized anionic comonomer in the polymer synthesis may be greater than about 0.2, greater than about 0.4, greater than about 0.5, greater than about 0.6, greater than about 0.7, from about 0.5 to about 0.7, or about 0.67.
[0167] The branched comonomer (B) may be formed from a functionalized comonomer (B) such as a trifunctional comonomer (B). This functionalized comonomer (B) acts as a dienophile in the Diels-Alder addition reaction. A representative trifunctional comonomer (B) dienophile is represented by formula (V):
[0168]
[0169] in:
[0170] L3 at each occurrence is optionally substituted with 1, 2 or 3 independently selected from C 1-6 Substitution of alkyl, halo, nitro, cyano, aryl and heteroaryl substituents;
[0171] L2 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 Substitution of alkyl, halo, nitro, cyano, aryl and heteroaryl substituents;
[0172] L1 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 Alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; and
[0173] D1, D2 and D3 are independently H, R 1G , R 1H , R 3G , R 3H or a protecting group (e.g., a silyl protecting group, a substituted silyl protecting group, a trialkylsilyl protecting group, a silyl ether protecting group, a trialkylsilyl ether protecting group, or a trimethylsilyl ether),
[0174] Where R 1G and R 1H is independently H, aryl or heteroaryl, wherein the aryl and heteroaryl are each optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cations; and
[0175] Where R 3G and R 3H are independently alkyl, aryl or aralkyl.
[0176] The multivalent branched comonomers cited herein, such as branched comonomer (B), can be incorporated into the polymer via an alkyne functional group or a protected alkyne functional group. The alkyne functional group can be located at a central position in the molecule, or at a terminal position in the molecule. The functionalized comonomer (B) can include a mixture of functionalized comonomers, or can include a pure composition of comonomers having essentially one molecular composition.
[0177] The functionalized comonomer (B) may be a relatively small molecule, such as 1,3,5-triethynylbenzene, or a relatively large molecule, such as a molecule comprising more than one aromatic group and three alkyne functional groups. The functionalized comonomer (B) may include one or more aromatic rings, one or more heteroaromatic rings, or a combination thereof. Where the functionalized comonomer (B) includes one or more heteroaromatic rings, one or more heteroatoms may be present, wherein the one or more heteroatoms are selected from nitrogen, oxygen and sulfur. The heteroaromatic ring may be pyridine or pyrazine. Representative trifunctional comonomers (B) may include one or more of the following structures:
[0178]
[0179] In some embodiments, the functionalized comonomer (B) may comprise a central atom, such as nitrogen or carbon, and may include one or more of the following structures:
[0180]
[0181] In some embodiments, one or more terminal alkyne groups are substituted with H.
[0182] In some embodiments, the functionalized comonomer (B) may include five or six functional groups, such as five or six alkyne groups. The functionalized comonomer B may include five or six functionalized aromatic rings to include hexa- or pentaphenylbenzene derivatives. Representative hexa- or pentaphenylbenzene dienophiles may include the following, wherein the "R" substituents within the molecule may be the same or may be different and may include alkynyl functional groups or hydrogen:
[0183]
[0184] In one embodiment, the multivalent comonomer has a structure according to a functionalized comonomer described herein, such as, for example, a trifunctional dienophile according to formula (VIII):
[0185]
[0186] In an embodiment, the functionalized anionic comonomer has a structure according to formula (VI):
[0187]
[0188] in:
[0189] R 1A , R 1B , R 1C , R 1D , R 1E and R 1F is independently aryl or heteroaryl, each of which is optionally substituted by 1, 2, 3, 4 or 5 independently selected from C1-6 Alkyl, halogen, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cation, and the limiting condition is R 1A , R 1B , R 1C , R 1D , R 1E and R 1F At least two of them are independently selected from SO3 by 1, 2, 3, 4 or 5 independently selected - X + PO3 2- X + 2 and COO - X + A substituent substituted aryl or heteroaryl, wherein X + Yes H + or cations;
[0190] A1 is arylene, heteroarylene, aralkylene or heteroaralkylene, each of which is optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl; and
[0191] A2 is absent, arylene or heteroarylene, wherein said arylene and heteroarylene are each optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl.
[0192] As described in this article, X + is a counter ion and can be H + , cations, alkali metal ions (such as Li + 、Na + , K + , Rb + and / or Cs + ), ammonium, substituted ammonium such as alkyl, aryl or heteroaryl substituted ammonium or a combination thereof. For example, ammonium can be [N(R 5A )(R 5B )(R 5C )(R 5D )] + , where R 5A , R 5B , R 5C and R 5D Independently H, C 1-6 Alkyl, aryl, aralkyl or heteroaryl.
[0193] In illustrative embodiments, the functionalized anionic comonomer of formula (VI) is:
[0194]
[0195] The branched ionomer polymer of formula (I) may further include a bifunctional linker (C) as shown in Scheme 1. The bifunctional linker may include an aryl or heteroaryl group, and as used herein, an arylene or heteroarylene group. In an embodiment, an arylene or heteroarylene group may include an aryl or heteroaryl group, may include more than one aryl or heteroaryl group, or may include a combination of one or more aryl and heteroaryl groups. Wherein there is a bifunctional linker (C) and the bifunctional linker (C) includes one or more, or more than one aryl or heteroaryl group, and the aryl or heteroaryl group may be the same or different aryl or heteroaryl groups. For example, one or more, or more than one aryl or heteroaryl group may include aryl and aryl (e.g., phenyl and phenyl to prepare biphenyl, or phenyl and naphthyl), or may include aryl and heteroaryl (e.g., phenyl and pyridyl).
[0196] In one embodiment, the bifunctional arylene group may be phenyl, naphthyl, anthracenyl, biphenyl, terphenyl, etc. or a combination thereof.
[0197] The functionalized comonomer (B), difunctional comonomer C and functionalized anionic comonomer described herein can be reacted together in a certain ratio to achieve a specific and desired ratio in the branched ionomer polymer composition. For example, the functionalized comonomer (B) can be present in an amount of 0.001 to 20 mole percent relative to the combination of anionic comonomer and difunctional comonomer C. In the foregoing, difunctional comonomer C may be present or may be completely absent.
[0198] In contrast, hyperbranching is produced by relatively high amounts of functionalized comonomer (B) when used in a ratio of greater than about 20 mole percent, greater than about 15 mole percent, greater than about 13 mole percent, greater than about 12 mole percent, about 13.3 mole percent, about 13.33 mole percent, or about 13.333 mole percent relative to the anionic comonomer (e.g., a relative amount of about 66 to 67 mole percent). In one embodiment, the hyperbranched ionomer polymer includes an amount of functionalized comonomer (B) in an amount of about 13.3 mole percent relative to the amount of anionic comonomer. In one embodiment, the hyperbranched ionomer polymer includes an amount of functionalized comonomer (B) in an amount of about 13.3 mole percent relative to the amount of anionic comonomer. In one embodiment, the hyperbranched ionomer polymer includes an amount of functionalized comonomer (B) in an amount of about 13.33 mole percent relative to the amount of anionic comonomer. In one embodiment, the hyperbranched ionomer polymer includes an amount of functionalized comonomer (B) in an amount of about 13.333 mole percent relative to the amount of anionic comonomer. In one embodiment, the hyperbranched ionomer polymer includes a functionalized comonomer (B) in an amount of about 20 mole percent relative to the amount of anionic comonomer. For example, to achieve hyperbranching, the molar ratio of the functionalized comonomer (B) and the difunctional comonomer C to the functionalized anionic comonomer in the Diels-Alder addition reaction may be greater than about 0.2 (equivalent to about 20 mole percent), greater than about 0.3 (equivalent to about 30 mole percent), greater than about 0.4 (equivalent to about 40 mole percent), greater than about 0.5 (equivalent to about 50 mole percent), greater than about 0.6 (equivalent to about 60 mole percent), greater than about 0.7 (equivalent to about 70 mole percent), between about 0.2 and about 0.8, between about 0.5 and about 0.75, between about 0.6 and about 0.7%, or about 0.67 (equivalent to about 67 mole percent). In the above cases, the difunctional comonomer C may be present or may not be present at all.
[0199] In one embodiment, a branched or hyperbranched ionomer polymer of formula (I) is used in a catalyst ink formulation. The catalyst ink formulation may include: (1) a polar solvent, (2) a branched and / or hyperbranched ionomer polymer having a structure of formula (I) as described herein and including any variants, (3) a branched and / or linear ionomer polymer, and (4) a catalyst. The catalyst ink formulation may include: (1) a polar solvent, (2) a hyperbranched ionomer polymer having a structure of formula (I) as described herein and including any variants, (3) a linear ionomer polymer, and (4) a catalyst. The catalyst ink formulation may include: (1) a polar solvent, (2) a branched ionomer polymer having a structure of formula (I) as described herein and including any variants, (3) a linear ionomer polymer, and (4) a catalyst. The catalyst ink formulation may include: (1) a polar solvent, (2) a hyperbranched ionomer polymer having a structure of formula (I) as described herein, including any variations, (3) a branched linear ionomer polymer, and (4) a catalyst.
[0200] The catalyst of the catalyst ink formulation may include a carbon-supported platinum support of various Pt particle sizes combined with carbon materials of various surface areas and sizes (that is, Pt / C); a carbon-supported Pt alloy support of various precious metal alloy particle sizes and alloy ratios combined with carbon materials of various surface areas and sizes (e.g., PtCo / C); or an MNC catalyst (e.g., where M is iron or cobalt) incorporating non-precious metal ions into a nitrogen-doped carbon support.
[0201] The amount of catalyst used may depend on the catalyst characteristics, the amount of solids in the catalyst ink, the ionomer to catalyst ratio, and / or other factors.
[0202] As used herein, the weight % of Pt / C catalyst means the total amount of Pt / C solid used, including the amount of Pt and carbon. For example, for the total mass used, whether the Pt / C is 40 weight % Pt and 60 weight % carbon or a different relative composition, the weight % of Pt / C remains the same.
[0203] In one embodiment, the amount of catalyst used may be between about 0.1 wt % and about 2.0 wt % based on solids content.
[0204] In one embodiment, the amount of catalyst used may be between about 0.1% w / v and about 25% w / v catalyst (eg, Pt / C, PtCo / C, and MNC catalysts) relative to the volume of the catalyst ink solvent.
[0205] In one embodiment, the catalyst ink composition may include between about 1 wt % and about 30 wt % of the ionomer polymer, and between about 70 wt % and about 99 wt % of the supported catalyst, based on the total solids content.
[0206] In one embodiment, the catalyst ink composition may include between about 10 wt % and about 30 wt % of the ionomer polymer, and between about 70 wt % and about 90 wt % of the supported catalyst, based on the total solids content.
[0207] In one embodiment, the catalyst layer may include between about 1 wt % and about 30 wt % ionomer polymer, and between about 70 wt % and about 99 wt % supported catalyst or solids content.
[0208] The linear ionomer polymer may include the structure of formula (IX):
[0209]
[0210] It is a linear sulfonated phenylated poly(phenylene) biphenyl and is denoted as sPPB-H + In another embodiment, the linear ionomer polymer may include a structure of formula (X):
[0211]
[0212] It includes sPPB-H + and a random copolymer of hydrophobic units, denoted as RCP-sPPB-H + In one embodiment, the linear ionomer polymer may include commercially available PFSA materials such as, but not limited to, long side chain PFSA ionomers (e.g. ), short side chain PFSA ionomers (e.g. ) and / or its similar derivatives (e.g., 3M ionomers). In one embodiment, the linear ionomer polymer is any linear ionomer polymer.
[0213] The branched or hyperbranched ionomer polymer may be disposed in a polar solvent, wherein the branched or hyperbranched ionomer polymer is placed, introduced or suspended in the polar solvent. The branched or hyperbranched ionomer polymer may be dispersed in a polar solvent. The branched or hyperbranched ionomer polymer may have a solubility in a polar solvent of about 0% to about 20%, about 0% to about 15%, about 0% to about 10%, about 0% to about 5%. In one embodiment, the branched or hyperbranched ionomer polymer has a solubility in a polar solvent of between about 0% and about 20%. The branched or hyperbranched ionomer polymer may be substantially insoluble in a polar solvent.
[0214] The linear ionomer polymer has a solubility in the polar solvent that is greater than the solubility of the branched or hyperbranched ionomer polymer. The polar solvent is contacted with the linear ionomer polymer, and the linear ionomer polymer can be completely dispersed (e.g., about 90% to about 100%), substantially completely dispersed (e.g., at least about 97%), or mostly (e.g., at least about 90%) in the polar solvent to form a solution in which the linear ionomer polymer is dispersed in the polar solvent.
[0215] As used herein, dispersed means that particles of the ionomer polymer are fairly uniformly distributed throughout the polar solvent, or that the ionomer polymer is soluble in the polar solvent and can be uniformly distributed throughout the polar solvent upon mixing.
[0216] In one embodiment, a linear ionomer polymer (e.g., sPPB-H + ) is at least about 97% dispersed in an alcohol (e.g., a low boiling alcohol as described herein). In one embodiment, a linear ionomer polymer (e.g., sPPB-H + ) is at least about 97% dispersible in a combination of water and an alcohol (eg, a low boiling point alcohol as described herein).
[0217] In one embodiment, for example, when the amount of branching is about 0.5 mol%, sPPB-H + The combination of sPPB-H and branched and / or hyperbranched polymers is at least about 97% dispersed in alcohol (e.g., a low boiling alcohol as described herein), or at least about 97% dispersed in a combination of alcohol (e.g., a low boiling alcohol as described herein) and water. In one embodiment, for example, when the amount of branching is about 1 mol%, sPPB-H + The combination of the sPPB-H and the branched and / or hyperbranched polymer is at least about 90% dispersed in an alcohol (e.g., a low boiling alcohol as described herein), or at least about 90% dispersed in a combination of an alcohol (e.g., a low boiling alcohol as described herein) and water. In one embodiment, for example, when the amount of branching is about 2 mol% or more, the sPPB-H +The combination with branched and / or hyperbranched polymers is partially dispersed (e.g., less than about 90%, less than about 80%, less than about 70%, less than about 60%, less than about 50%, less than about 40%, less than about 30%, or about 33%) in an alcohol (e.g., a low boiling alcohol as described herein), or partially dispersed (e.g., less than about 90%, less than about 80%, less than about 70%, less than about 60%, less than about 50%, less than about 40%, less than about 30%, or about 33%) in a combination of an alcohol (e.g., a low boiling alcohol as described herein) and water. In some embodiments, the polar solvent may include water, alcohols (e.g., methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol), ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone). In some embodiments, the polar solvent is a low boiling alcohol. Low boiling alcohols may include boiling points below 120° C., below 100° C., below 90° C., below 85° C., below 80° C., below 70° C., between about 60° C. and about 80° C., or between about 60° C. and about 85° C. Examples of low boiling alcohols include methanol, ethanol, isopropanol, n-propanol, tert-butanol, n-butanol, etc. In a preferred embodiment, the alcohol is methanol or isopropanol.
[0218] In some embodiments, the polar solvent comprises an alcohol, a ketone, water, or a combination thereof. In some embodiments, the polar solvent comprises a combination of more than one component, such as an alcohol and water; more than one different alcohol and water; or one or more of the same or different alcohols, one or more of the same or different ketones, and water. In embodiments where the polar solvent comprises an alcohol and water, the composition of the polar solvent may be about 1:1 volume to volume ratio of water to alcohol, about 1:2 volume to volume ratio of water to alcohol, about 1:3 volume to volume ratio of water to alcohol, about 1:4 volume to volume ratio of water to alcohol, about 1:2.5 volume to volume ratio of water to alcohol, or about 1:3.5 volume to volume ratio of water to alcohol.
[0219] In some embodiments, the amount of linear ionomer polymer added is an amount that allows the branched or hyperbranched ionomer polymer to be dispersed in the polar solvent.
[0220] In some embodiments, the branched or hyperbranched ionomer polymer may be present in the catalyst ink formulation in an amount from about 0.01 wt % to about 10 wt % of the total solids content.
[0221] The amount of the linear ionomer polymer may be less than, equal to, or greater than the amount (by mass) of the branched or hyperbranched ionomer polymer used. For example, the ratio of the mass of the linear ionomer polymer to the mass of the branched ionomer polymer may be between about 1:2 and about 3:1, between about 1:1 and about 2:1, between about 1.8:1 and about 2.2:1, between about 1.9:1 and about 2.1:1, or about 2:1. In one embodiment, the ratio of the mass of the linear ionomer polymer to the mass of the branched ionomer polymer is about 2:1.
[0222] The branched or hyperbranched ionomer polymer in combination with the linear ionomer polymer may be present in the polar solvent at from about 0.01% w / v to about 35% w / v, about 0.01% w / v to about 30% w / v, about 0.01% w / v to about 25% w / v, about 0.01% w / v to about 20% w / v, about 0.01% w / v to about 15% w / v, about 0.01% w / v to about 10% w / v, about 0.01% w / v to about 5% w / v, less than about 20% w / v, or less than about 10% w / v.
[0223] In one embodiment, the catalyst ink formulation includes an amount of branched or hyperbranched ionomer polymer and an amount of linear ionomer polymer, wherein the total amount of branched, hyperbranched and linear ionomer polymers dispersed in the polar solvent is from about 0.1% w / v to about 25% w / v.
[0224] At concentrations above the aforementioned concentrations, the stability of dispersions including insoluble branched or hyperbranched ionomer polymers may be affected. This may inhibit the incorporation of branched or hyperbranched ionomers into catalyst ink formulations and inhibit their effective incorporation into polymer membranes, thereby reducing electrical properties and power density advantages, as described in detail in the examples below.
[0225] Examples of anionic polyphenylene monomers, oligomers and polymers are provided below. Example 1 describes the controlled synthesis of sulfonated comonomers and their use in the synthesis of sulfonated branched oligophenylene and hyperbranched ionomer polymers (HB-sPPT-H + ) in the literature, both of which allow precise control of the position and amount of the sulfonic acid groups.
[0226] In one embodiment, the branched and / or hyperbranched ionomeric polymers described herein may be incorporated into ionomeric polymer membranes.
[0227] The ionomeric polymer membrane may include a mechanical reinforcement and an ionomeric binder coupled to the mechanical reinforcement.
[0228] The ionomeric polymer membrane may include a substrate and an ionomeric adhesive coupled to the substrate.
[0229] The ionomeric binder may be coupled directly or indirectly to the mechanical reinforcement or substrate via covalent bonding, ionic bonding, hydrogen bonding, van der Waals forces, and / or metallic bonding.
[0230] The mechanical reinforcement or substrate may include a porous polymeric material. The porous polymeric material may be any polymeric material that includes pores. The porous polymeric material may be, for example, a linear sulfonated phenylated poly(phenylene) ionomer, such as a linear sulfonated phenylated poly(phenylene) biphenyl (sPPB-H) of formula (IX). + ) ionomer, and / or expanded polyethylene (ePE).
[0231] In one embodiment, the ionomer binder may include a branched ionomer polymer of formula (I), or a hyperbranched ionomer polymer of formula (I) and all iterations disclosed herein. The branched or hyperbranched ionomer polymer of the ionomer binder may include an amount from about 0.5 wt % to about 99 wt %, about 0.5 wt % to about 50 wt %, about 0.5 wt % to about 25 wt %, or about 0.5 wt % to about 15 wt %.
[0232] In one embodiment, the ionomer binder may further include a linear ionomer. For example, the linear ionomer polymer of the ionomer binder is a linear sulfonated phenylated poly(phenylene) biphenyl (sPPB-H + ) ionomers, including sPPB-H + and a random copolymer of hydrophobic units, a PFSA material, or a combination thereof.
[0233] In one embodiment, the amount of linear ionomer of the ionomer binder can be less than, equal to, or greater than the amount (by mass) of the branched or hyperbranched ionomer polymer used. For example, the ratio of the mass of the linear ionomer polymer to the mass of the branched ionomer polymer can be between about 1:1 and about 3:1, between about 1:1 and about 2:1, between about 1.8:1 and about 2.2:1, between about 1.9:1 and about 2.1:1, or about 2:1. In one embodiment, the ratio of the mass of the linear ionomer polymer to the mass of the branched ionomer polymer is about 2:1.
[0234] In one embodiment, the branched or hyperbranched ionomer of the ionomer binder is present in an amount from about 0.5 wt % to about 10 wt %, and the linear sPPB-H + The ionomer is present in an amount about equal to or greater than the mass of the branched or hyperbranched ionomer of the ionomer binder.
[0235] The ionomer binder may include a combination of branched and hyperbranched ionomer polymers without linear ionomer polymers; a combination of linear and hyperbranched ionomer polymers without branched ionomer polymers; a combination of branched and linear ionomer polymers without hyperbranched ionomer polymers.
[0236] The catalyst layer described herein may be applied to an ionomeric polymer membrane to form a catalyst coated ionomeric polymer membrane.
[0237] In one embodiment, the ionomer polymer membrane described herein may further include a catalyst layer to form a catalyst-coated ionomer polymer membrane, wherein the catalyst layer is in contact with the ionomer polymer membrane.
[0238] The catalyst layer or a component of the catalyst layer may be in contact with a mechanical reinforcement of an ionomer polymer membrane, with an ionomer binder of an ionomer polymer membrane, or with both a mechanical reinforcement and an ionomer binder of an ionomer polymer membrane. The catalyst layer or a component of the catalyst layer may be in contact with a substrate of an ionomer polymer membrane, with an ionomer binder of an ionomer polymer membrane, or with both a substrate and an ionomer binder of an ionomer polymer membrane.
[0239] The catalyst layer may be formed from a catalyst ink. The catalyst layer may be formed from a catalyst ink formulation as described above and below herein. The formation of the catalyst layer may include applying a catalyst ink formulation and subsequently removing a solvent. The formation of the catalyst layer may include printing using a catalyst ink formulation.
[0240] The catalyst layer comprises a catalyst ink composition with at least about 90% of the solvent removed, at least about 95% of the solvent removed, at least about 97% of the solvent removed, at least about 99% of the solvent removed, substantially all detectable solvent removed, or about 97% of the solvent removed. In one embodiment, about 97% of the solvent is removed from the catalyst ink formulation when forming the catalyst layer.
[0241] The solvent of the catalyst ink formulation may be removed by techniques known in the art for solvent removal (eg, ambient temperature and pressure evaporation, high pressure or high temperature evaporation, extraction of the solvent, filtration, absorption, etc.).
[0242] The catalyst layer may include catalysts of various Pt particle sizes combined with carbon materials of various surface areas and sizes, such as platinum-on-carbon supports (that is, Pt / C); Pt alloy supports of various precious metal alloy particle sizes and alloy ratios combined with carbon materials of various surface areas and sizes (e.g., PtCo / C); or MNC catalysts (e.g., where M is iron or cobalt) doped with non-precious metal ions in nitrogen-doped carbon supports. The catalyst-coated ionomer polymer membrane may include Pt / C, PtCo / C, MNC catalysts, or combinations thereof.
[0243] The catalyst layer may further include an additive.
[0244] The catalyst layer may include a combination of catalysts; a branched ionomer polymer, a hyperbranched ionomer polymer, a linear ionomer polymer, or a combination thereof; and an additive. The catalyst layer may further include a residual solvent.
[0245] As used herein, the catalyst layer ionomer polymer may include a branched ionomer polymer, a hyperbranched ionomer polymer, a linear ionomer polymer, or a combination thereof.
[0246] The amount of catalyst, branched ionomer polymer, hyperbranched ionomer polymer and linear ionomer polymer in the catalyst layer is from about 50 wt % to about 100 wt % based on the total weight of the catalyst layer.
[0247] The catalyst layer catalyst and catalyst layer ionomer polymer may account for at least 90 weight percent of the catalyst layer, the catalyst and ionomer polymer may account for at least 94 weight percent of the catalyst layer, the catalyst and ionomer polymer may account for at least 95 weight percent of the catalyst layer, the catalyst and ionomer polymer may account for at least 96 weight percent of the catalyst layer, the catalyst and ionomer polymer may account for at least 97 weight percent of the catalyst layer, or the catalyst and ionomer polymer may account for at least 98 weight percent of the catalyst layer.
[0248] The catalyst layer may include about 10 wt % to about 30 wt % ionomer polymer and about 70 wt % to about 90 wt % catalyst.
[0249] The ionomer binder of the ionomer polymer membrane may comprise at least 50 wt % of the weight of the ionomer polymer membrane, at least 60 wt % of the weight of the ionomer polymer membrane, at least 70 wt % of the weight of the ionomer polymer membrane, at least 80 wt % of the weight of the ionomer polymer membrane, at least 90 wt % of the weight of the ionomer polymer membrane, or from about 60 wt % to about 90 wt % of the weight of the ionomer polymer membrane.
[0250] The linear ionomer of the ionomer adhesive may include about 0 wt%, 1 wt%, about 5 wt%, about 10 wt%, about 15 wt%, about 20 wt%, about 25 wt%, or about 30 wt%. In one embodiment, the linear sPPB-H of the ionomer adhesive + The ionomer may comprise about 15 wt % of the weight of the ionomer adhesive.
[0251] The branched and / or hyperbranched ionomer polymer of the ionomer binder may comprise from about 0.5 wt % to about 25 wt % of the weight of the ionomer binder, or from about 0 wt % to about 25 wt % of the weight of the ionomer binder.
[0252] The linear ionomer polymer of the ionomer binder is present in an amount about equal to or greater than the amount of the branched or hyperbranched ionomer polymer of the ionomer binder.
[0253] Optimization of the weight % of linear ionomers is discussed in more detail in Examples 1-4, and thus, the composition of the ionomer binder can be guided by the stability of the ionomer polymer membrane comprising the branched or hyperbranched ionomer polymer (e.g., reducing delamination of the catalyst layer from the substrate).
[0254] In embodiments of branched or hyperbranched ionomer polymer membranes, the substrate or mechanical reinforcement, ionomer binder, and catalyst layer are substantially free of halogens. As used herein, "substantially free" means that the branched or hyperbranched ionomer polymer membrane, ionomer binder, and catalyst layer each include less than about 1% halogen, less than about 0.5% halogen, less than about 0.01% halogen, or less than about 0.001% halogen. Some measurable levels of halogens may be introduced during operation, for example, as halide salts (e.g., NaCl), as synthesis or processing impurities, or as trace gases.
[0255] The ionomer polymer film may have a top surface and a bottom surface, such as would exist in a formation such as a sheet (including a sheet that is rolled, folded, or deformed in another manner).
[0256] The catalyst layer may be in contact with only the top surface of the ionomer polymer membrane, only the bottom surface of the ionomer polymer membrane, or both the top and bottom surfaces of the ionomer polymer membrane.
[0257] A bilayer is formed when the catalyst layer contacts only the top surface or only the bottom surface of the ionomer polymer membrane. The bilayer can be used as a two-layer membrane electrode assembly.
[0258] A trilayer is formed when the catalyst layer contacts both the top and bottom surfaces of the ionomer polymer membrane. The trilayer can be used as a trilayer membrane electrode assembly.
[0259] The double or triple layer catalyst coated ionomer polymer membrane may be in a planar form, such as a sheet. The sheet may be flat, curled, folded or otherwise deformed. For example, the catalyst coated ionomer polymer membrane may be a curled sheet to form a roll having a size such as 30 cm wide, a length such as 1 to 1000 meters, or a length such as 10 to 100 meters.
[0260] In one embodiment, the catalyst layer of the catalyst-coated ionomer polymer membrane can act as an anode or a cathode. When only one surface of the ionomer polymer membrane is in contact with the catalyst layer, the catalyst layer is an anode or a cathode. When both surfaces of the ionomer polymer membrane are in contact with the catalyst layer, one catalyst layer is an anode and the other catalyst layer is a cathode.
[0261] Generally speaking, the anode is the electrode where oxidation occurs during an electrochemical reaction, and the cathode is the electrode where reduction occurs during an electrochemical reaction.
[0262] Whether a catalyst layer is an anode or a cathode can be determined by the orientation of the catalyst layer in a product such as a fuel cell. Whether a catalyst layer is an anode or a cathode can be determined by a combination of the orientation of the catalyst layer in the fuel cell and the amount of catalyst present. In a fuel cell, the anode is the fuel such as hydrogen (H2) that is oxidized to release electrons and protons (H + ) electrodes. The electrons are then attracted through an external circuit to perform useful operations, while the protons (H + ) migrates through the electrolyte to the cathode. In a fuel cell, the cathode is where oxygen (O2) is reduced to react with protons (H + ) combine to form water (H2O) electrode.
[0263] In an electrolyzer, the anode is where water (H2O) is oxidized by an electrochemical reaction to produce oxygen (O2), protons (H + ) and electron (e - ) electrodes.
[0264] In an electrolyzer, the cathode is where the protons (H + ) is an electrode that produces hydrogen (H2) through electrochemical reduction.
[0265] The branched or hyperbranched ionomer polymer film may have a relative humidity of from about 0.001 mS cm-1 at a relative humidity of 30% to 100% when measured using AC impedance spectroscopy (electrochemical impedance spectroscopy) at a temperature between about 20° C. to about 90° C. or about 50° C. to about 90° C. -1 To about 1000mS cm -1 , from about 0.001mS cm -1 To about 750mS cm -1 , from about 0.001mS cm -1 To about 450mS cm -1 , from about 1mS cm -1 To about 1000mS cm -1 , greater than about 0.001 mS cm -1 , greater than about 1 mS cm -1 or less than about 1000mS cm-1 The ionic polymer membrane may have a proton conductivity (eg, ex situ conductivity, in-plane) of from about 1 mS cm in water at about 80° C. when measured using AC impedance spectroscopy (electrochemical impedance spectroscopy). -1 To about 1000mS cm -1 or about 50mS cm -1 To about 450mS cm -1 Proton conductivity (e.g., ex situ conductivity, in-plane).
[0266] The branched or hyperbranched ionomer polymers as described herein can be incorporated into a catalyst layer of a fuel cell, electrolyzer, or another electrochemical device.A fuel cell, electrolyzer, or another electrochemical device can include a catalyst layer.
[0267] For example, the branched or hyperbranched ionomer polymer can be incorporated into a catalyst layer of a fuel cell, electrolyzer, or another electrochemical device in an amount from about 5 wt % to about 45 wt % solids, from about 10 wt % to about 45 wt %, from about 15 wt % to about 45 wt %, from about 30 wt % to about 45 wt %, from about 5 wt % to about 30 wt %, from about 15 wt % to about 45 wt %, from about 30 wt % to about 45 wt %, from about 10 wt % to about 30 wt %, from about 10 wt % to about 20 wt %, or from about 15 wt % to about 30 wt % in the catalyst layer.
[0268] In some embodiments, the branched or hyperbranched ionomer polymers of the present disclosure are incorporated into a cation exchange resin.
[0269] When exposed to Fenton's reagent at 80°C, 1 atm for greater than 0 to 180 minutes, or greater than 0 to 90 minutes, or greater than 0 to 60 minutes, the branched or hyperbranched ionomer polymers described herein may exhibit less than about 20% or less than about 10% mass loss.
[0270] When the acid (or protonated) form (e.g. -SO3-H + ) membrane cations are exchanged into their conjugate base sodium counterparts (e.g., -SO3-Na + )) is evaluated by immersing the sample in a 1 M NaCl solution at pH 7 for 48 hours; the acidic form is then titrated to pH 7 using a standard titrant (e.g., 0.01 M NaOH solution, Sigma Aldrich). The branched or hyperbranched ionomer polymers described herein may have a molecular weight of from about 2 to about 4.5 meq g -1 or from about 2.9 to about 3.7 meq g -1The ion exchange capacity (IEC) of the titrant is 1. The IEC can be calculated by the volume and molarity of the titrant used and the dry mass of the sample being titrated. It will be appreciated by one of ordinary skill in the art that titrations can also be performed with other bases (e.g., KOH solution) and that the relative ions cations can be exchanged, for example, by exposure to sodium sulfonate salts with, for example, KCl to result in full or partial potassium salts (e.g., -SO3-K + )form.
[0271] Examples
[0272] Example 1
[0273] Non-conformal particles of hyperbranched sulfonated phenylated poly(phenylene) ionomers as catalyst layers in PEMFCs Proton conduction pathway
[0274] Poor electrochemical kinetics, high ionic resistance and high mass transport resistance within the catalyst layer (CL) are the main parameters leading to the poor performance of proton exchange membrane fuel cells (PEMFCs) using hydrocarbon-based proton conducting ionomers.
[0275] In the catalyst ink, the Pt-supported carbon catalyst particles agglomerate into cohesive aggregates containing primary pores with diameters ranging from about 1 nm to about 30 nm. When deposited to form the anode and cathode CLs, the cohesive aggregates aggregate into larger aggregates and form larger secondary pores with diameters ranging from about 20 nm to about 200 nm. As described in the cohesive aggregate model, the secondary pores facilitate the diffusion of gases and the transport of water within the CL. Polyelectrolytes (such as perfluorosulfonic acid (PFSA) ionomers, commonly referred to as trademarks) ) is also included in the ink dispersion to encapsulate and bind the Pt / C aggregates, providing proton conduction pathways within the CL.
[0276] Thin coatings of ionomers can introduce O2 permeation barriers between the interstitial void space within the primary pores and the catalyst particles and on the surface of the secondary pore structure. The permeation barriers introduce mass transport resistance that cannot be explained by the cohesive model alone. Therefore, a lot of research has been done to understand O2 permeation through ionomer films, the effect of the chemistry of the ionomer, the effect of the porosity of the support, and the effect of the catalyst ink composition on mass transport limitations within the CL.
[0277] Herein, non-size-expandable, non-conformal, hyperbranched sulfonated poly(phenylene) ionomer particles (HB-sPPT- + ) introduced a direct pathway for proton conduction in hydrocarbon ionomer-based CLs, resulting in an 8-fold decrease in the ionic resistance of the CLs, a 71% increase in catalyst mass activity, and a >90% increase in power at 0.6 V (H2 / air) compared to the state-of-the-art hydrocarbon ionomer-based CLs.
[0278] When used in a perfluorosulfonic acid (PFSA) ionomer-based PEMFC, the incorporation of HB-sPPT-H + Benefits of Ionomer Particles These results dispel a commonly held belief that hydrocarbon ionomers have gas permeability and electrochemical activity limitations and open previously unexplored avenues for ionomer development for non-fluorinated, all-hydrocarbon PEMFCs.
[0279] Previously manufactured hydrocarbon substitutes contain aromatic units that have inherently greater thermochemical flexibility. Unlike PFSAs, polycyclic aromatic hydrocarbons and polyheterocyclic polymers can be synthesized from readily available synthetic chemical feedstocks in a typical organic polymer chemistry laboratory. Compared to PFSAs, hydrocarbon ion-conducting polymers exhibit relatively low gas permeabilities, and thus have low gas permeabilities when used as proton exchange membranes (PEMs).
[0280] Sulfonated poly(arylene ether) and sulfophenylated polyphenylene ionomers can exhibit improved chemical stability relative to PFSA. In one illustrative example, biphenyl comonomer (sPPB-H + ) provides improved stability at the expense of reduced ionic conductivity.
[0281] Also explore sPPB-H + Cross-linking and molecular branching have been investigated as a means to reduce the dimensional expansion of such hydrocarbon ionomers when cast into PEMs and to improve the mechanical integrity. A notable observation is that the conductivity of these materials increases as water absorption decreases, indicating that the increase in proton concentration outweighs any decrease in proton mobility. However, due to excessive levels of branching, the ionomers are insoluble and unsuitable for PEM formation.
[0282] Fully hydrocarbon-based MEA achieves greater than 1.5 Wcm -2 Output power (under H2 / O2, atmospheric pressure) using linear sPPB-H + As binders for PEMs and CLs. Notably, in the mass transport region of the fuel cell polarization curve, the performance of such hydrocarbon ionomers is observed to exceed This is attributed to the high CL porosity. However, the ionic resistance within the hydrocarbon-based CL is Three times the value reported for the base CL.
[0283] Inspired by the AEMFC performance of insoluble radiation-grafted ETFE anion exchange materials used in AEMFC CL, a hyperbranched sulfonated polyphenylene copolymer (HB-sPPT-H + ) particles are included in the CL in order to reduce the ionic resistance in the CL, e.g. Figure 1A and 1F shown.
[0284] HB-sPPT-H + is through the difunctional diene comonomer TEAsBTC and Fig.10 The trifunctional dienophilic comonomer 1,3,5-tri(4-ethynylphenyl)-benzene (3) prepared as shown was obtained by a [4+2] Diels-Alder addition reaction. The dienophilic comonomer (3) was obtained via a three-step synthesis, starting from the cyclotrimerization reaction of 4-iodoacetophenone and p-toluenesulfonic acid to obtain the intermediate (1) with a yield of 82%. A Sonogashira coupling reaction was carried out between the intermediate (1) and trimethylsilyl acetylene, and a second intermediate (2) was obtained after precipitation with a yield of 92%, which was used without further purification. A deprotection step of the silicon group was carried out under mild conditions (MeOH / K2CO3), and (3) was obtained after purification on a silica gel plug with a yield of 73%. TEAsBTC and (3) were reacted together in de-argon nitrobenzene by stirring at 170°C for 5 days. After the polymerization was completed, the precipitate formed was filtered to obtain HB-sPPT-NEt3+. Synthesis scheme and subsequent exchange to the protonated form (HB-sPPT-H + ) is displayed in Fig.10 In. HB-sPPT-H + The 3D representation of the chemical structure is as follows Figure 1A shown.
[0285] like Figure 1E As shown, even after stirring in common laboratory polar protic solvents, HB-sPPT-H + The powder also exhibited a sand-like quality, allowing it to be mechanically ground. + and HB-sPPT-H for catalyst ink preparation + The pictures obtained by UV optical microscopy are shown in Figure 1B HB-sPPT-H was measured using ImageJ processing software + The size of the particles was found to be in the range of 30 to 100 microns, but appeared to be at least partially formed by agglomerates of smaller particles. The agglomerates were dispersed (e.g., by grinding, milling, etc.) to obtain smaller particles with an average particle size of 7.0 ± 2.1 μm, such as Figure 1C shown.
[0286] Determination of HB-sPPT-H by dynamic vapor sorption (DVS) measurement + Water absorption of the powder at different relative humidity at 80 °C and compared with that of the linear sPPB-H + sPPB-H + An exemplary structure of is shown in formula (IX):
[0287]
[0288] The absorption isotherm obtained is as follows Figure 1D As shown. At 75% RH, with linear sPPB-H + (40 wt%) compared to HB-sPPT-H + It has a slightly lower water absorption of 32 wt%. Compared with the linear sPPB-H which undergoes dimensional expansion (145 vol%) + Different membranes, HB-sPPT-H + It showed no evidence of dimensional expansion and remained sand-like in boiling water. The relatively low branching of the polymer (≤2 mol%) may reduce water absorption but increase proton conductivity when cast as a membrane, which may lead to the + However, due to their insolubility, the intrinsic ionic conductivity of the particles was not measured.
[0289] Detection of HB-sPPT-H using in situ fuel cell electrochemical characterization + Effects on hydrocarbon-based and PFSA-based catalyst coated membranes (CCMs). + Ionomers are insoluble in alcohols, so use as the only ionomer in the CL results in rapid delamination of the catalyst from the membrane and in a non-functional CCM. To avoid this, HB-sPPT-H + With straight chain sPPB-H + Ionomer or Used in combination with ionomers. Linear sPPB-H + The ionomer content in CL is usually 15 wt%, while The ionomer content of HB-sPPT-H is usually 30% by weight. + The linear ionomer ratios were adjusted to these total wt %. Based on three replicate measurements of triplicate samples, Figure 2A and 2B It is shown that 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + The combination produces the best power performance.
[0290] for Figure 3A and 3B The PFSA-based CCM shown in Figure 1 produced 5 wt% HB-sPPT- + +25% by weight Improved compositions of ionomers.
[0291] The display performance enhancement is due to the addition of HB-sPPT-H +The mass of the linear ionomer was reduced compared with that of the ionomer containing 10 wt% linear sPPB-H + and 25 wt% The CL comparison of ionomers is shown in Figures 4A to 4F , Figures 5A to 5F and Tables 1 and 2 below.
[0292] Table 1: HB-sPPT-H + and linear sPPB-H + and Fuel cell data for ionomer-made CCMs.
[0293]
[0294]
[0295] a = peak power density on the power density curve, b = power density corresponding to 0.6 V on the polarization curve, c = Tafel slope (in mV / decade), d = mass activity derived from the effective current density at 0.9 V (corrected for H2 overshoot and ohmic losses) and catalyst loading, e = specific activity derived from the effective current density at 0.9 V (corrected for H2 overshoot and ohmic losses) and ECSA, f = CL internal ionic resistance derived from the linear intercept of the low frequency resistance equal to the x-axis under H2 / N2, g = electrochemical surface area determined from the cyclic voltammogram, h = intercept of the HFR with the x-axis under H2 / O2, I = charge transfer resistance, diameter of the semicircle of the Nyquist plot under H2.
[0296] Table 2: CCM hyperbranched sPPB-H + and Ionomer fuel cell data.
[0297]
[0298]
[0299] A direct comparison was made for the following modified CCMs: 15 wt% linear sPPB-H + Ionomer (hereinafter referred to as CCM 1), 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + (CCM 2), 30 wt% Ionomer (CCM 3) and modified 5 wt% HB-sPPT-H + +25% by weight Ionomer-based CCM (CCM 4).
[0300] The polarization and power curves under H2 / O2 operation are shown in Fig. 6A The extracted data listed in Table 3 show that CCM 2 (1430 mW cm -2 ) has a peak power density higher than CCM 1 (1240 mW cm -2 ) is 15% higher, but is comparable to the PFSA-based CCM 3 (1470mWcm -2 ) and CCM 4 (1490 mW cm -2 ) are similar. A greater improvement in power performance was observed under H2 / air operation ( Figure 6B ), that is, CCM 2 (876 mW cm -2 ) achieves a peak power density higher than CCM 1 (655mW cm -2 ) is 34% higher and the power density at 0.6V is increased by 92% (685mW cm -2 , and CCM 1 is 356 mW cm -2 ). Under H2 / air operation, the peak power density of CCM 4 is also 11% greater than that of CCM 3.
[0301] To better understand the differences in the obtained power density curves, the low current density region was further investigated by Tafel analysis. Figure 6C The data replotted in were corrected for ohmic losses and H2 overshoot, from which the mass and specific activities of the CCMs were calculated (Tables 3 to 4). It was observed that the Tafel slopes for all CCMs were within the range of each other, with an average value of -73 mV dec -1 , and compared with previous studies on sPPB-H + The values reported for the ionomers are similar to the expected values for ORR catalysis on Pt. As shown in Tables 3 to 4, the extracted values of the mass activity of CCM 1 and CCM 2 (I m(0.9V) ) are 17 and 29 mA mg respectively -1 Pt , while the values for CCM 3 and CCM 4 are 54 and 70 mA mg respectively -1 Pt Similarly, the specific activity (I s(0.9V) ) are 159 (CCM 1), 283 (CCM 2), 350 (CCM 3) and 424 μAcm -2 Pt(CCM 4). It is worth noting that HB-sPPT-H + The presence of ionomer increases the specific activity of hydrocarbon-based CCM by 78% and that of PFSA-based CL by 21%. The calculated activity and charge transfer resistance R at 0.8 V ct(0.8V) Reduce consistency, such as Fig.6DAs shown in the Nyquist plot in Tables 3 and 4. + When included in CL, CCM 1 and CCM 2 (43 and 41 m 2 g -1 Pt ) and when compared to CCM 3 (62m 2 g -1 Pt ) and CCM 4 (60m 2 g -1 Pt ) when the ECSA value (such as Fig. 6E This indicates that HB-sPPT-H + With straight chain sPPB-H + and The ionomers together contribute to the overall activation of the Pt catalyst, and it is noted that the lower ECSA values for the lower ionomer contents shown in Figures 4 to 5 are likely due to the more discontinuous proton conduction pathways associated with subcritical ionomer contents. m(0.9V) and R ct(0.8V) The change in corresponds to the change in the intrinsic catalytic activity of the Pt surface, which is related to Compared with sPPB-H + The catalytic activity of HB-sPPT-H + It is speculated that the degree of sulfonate and phenyl adsorption on hydrocarbon ionomers is the main reason for the decrease in specific activity.
[0302] From the H2 / O2 Nyquist plot ( Fig.6D and Tables 3 to 4), the R HFR is ~70mΩcm 2 , and the PEM thickness is 25μm R of CCM HFR Yes ~ 60mΩcm 2 Therefore, it is found that the membrane ohmic losses of each CCM are very similar, and although the HB-sPPT-H under H2 / air operation + The significant improvement in power performance can be attributed in part to the observed increase in catalytic activity, but the reduced concentration resistance at higher current densities must play a larger role.
[0303] To investigate this, EIS measurements were performed in a H2 / N2 environment, where the intercept of the second linear region with the real axis corresponds to R ionic-CL / 3 +R HFR .like Fig. 6F As shown in the values in Tables 3 to 4, the HB-sPPT- +CCM 2 has a higher resistance than CCM 1 (598mΩcm 2 ) 8 times smaller R ionic-CL (73mΩcm 2 ), which indicates that due to the HB-sPPT-H + Ionomers, proton conductivity is significantly higher. Compared with all PFSA-based CCM 3 (115mΩcm 2 ) compared to HB-sPPT-H + PFSA-based CCM 4 (98mΩcm 2 ) is less than that observed for hydrocarbon-based CCMs, but is likely due to the coordination network that the Nafion ionomer is able to form. The PFSA-based CCMs show higher ionic conductivity overall. This coordination network is also the expected reason for the higher ECSA calculated for the PFSA-based CCMs compared to the hydrocarbon-based CCMs. + The 5 wt% HB-sPPT-H + + 10 wt% linear sPPB-H + CCM 2(73mΩcm 2 ) has the lowest ionic resistance.
[0304] Table 3: HB-sPPT-H + 、Linear sPPB-H + and Comparison of fuel cell data for ionomer-made CCMs.
[0305]
[0306]
[0307] a = peak power density on the power density curve, b = power density corresponding to 0.6 V on the polarization curve, c = Tafel slope (in mV / decade), d = mass activity derived from the effective current density at 0.9 V (corrected for H2 overshoot and ohmic losses) and catalyst loading, e = specific activity derived from the effective current density at 0.9 V (corrected for H2 overshoot and ohmic losses) and ECSA, f = CL internal ionic resistance derived from the linear intercept of the low frequency resistance equal to the x-axis under H2 / N2, g = electrochemical surface area determined from the cyclic voltammogram, h = intercept of the HFR with the x-axis under H2 / O2, I = charge transfer resistance, diameter of the semicircle of the Nyquist plot under H2 / O2.
[0308] Table 4: HB-sPPT-H + and Comparison of fuel cell data for ionomer-made CCMs.
[0309]
[0310] To further elucidate the origin of the enhanced higher power performance at higher current density, Figures 7A to 7D The SEM micrographs of the comparative CCMs are shown in FIG. + The addition of ionomer particles increases the thickness of the CL. CCM 1 has a CL thickness of ∼10 μm; however, + CCM 2 with a similar overall 15 wt% ionomer content exhibits a CL thickness of ˜13 μm. Figures 7C to 7D As shown, in the presence of HB-sPPT-H + In the case of HB-sPPT-H particles, a similar increase in CL thickness of ∼3 μm was observed for PFSA-based CCMs. + The thicker CL is attributed to the relatively large size of individual particles, such as Figure 1B and 1C As shown, these particles are micrometer-sized and may act as pore-forming materials.
[0311] Table 5: 15 wt% linear sPPB-H+ (CCM 1), 5 wt% HB-sPPT-H++10 wt% linear sPPB-H+ (CCM 2), 30 wt% (CCM 3) and 5 wt% HB-sPPT-H++25 wt% BET analysis of CCM prepared by CL (CCM 4).
[0312]
[0313] i = BET SA measured in the range of 0.05 to 0.2 N2 partial pressure, ii = SA of mesopores, SA>2nm, calculated from the slope of the t-diagram, iii = SA of micropores, SA<2nm is SA 总 The difference between the mesopores SA>2nm, iv = total pore volume V 总 Calculated from the total adsorbed gas at 0.98 N2 partial pressure, v = volume of micropores V<2nm from the intercept of the t-diagram.
[0314] The N2 porosimeter method was used to test the HB-sPPT-H + The adsorption and desorption isotherms of CCM are shown in Fig. 7EThe observed isotherms are typical type II isotherms, which are known to have a high degree of microporosity and a sharp rise in isotherms when operated under low partial pressure conditions. As shown in Table 5, the BET surface areas (BET SA) of CL prepared from CCM 1, CCM 2, CCM 3, and CCM 4 were calculated to be 633, 531, 174, and 261 m, respectively. 2 g -1 碳 The former is similar to Pt / C (639m 2 g 碳 -1 , 666m 2 g -1 碳 ), indicating that sPPB-H + Not like However, for For hydrocarbon-based CCMs, a significant decrease in CL porosity was observed, with the volume of larger mesopores + macropores being 10x lower than that of hydrocarbon-based CCMs. These results suggest that Ionomers coat the cohesive aggregates of the carbon-supported catalyst, thereby blocking the native pore structure therein. In contrast, hydrocarbon ionomers do not, and therefore gas transport is less hindered, leading to much higher power performance at high current densities when air is used as the oxidant.
[0315] Compared with CCM 1, HB-sPPT-H + Addition to the hydrocarbon-based CCM resulted in a ∼16% decrease in BET SA, but showed larger pores (0.53 cm 3 g -1 碳 ),Depend on Figure 8 The similarity slope of the t-graph and Figure 7F The similarly larger area under the pore size distribution curve shown in . Furthermore, the large improvement in power performance at high current density cannot be explained by porosimetry alone, given the increase in CL thickness. Instead, it seems to be related to the 8x lower ionic resistance in the CL and, therefore, the concentration resistance related to proton transport. However, for Compared with CCM 4, HB-sPPT-H + The ionomer resulted in a 50% increase in the BET SA, which is most likely due to This is believed to be Figure 6B This is the reason for the improvement in the medium and high current density regions, and also the reason for the improvement in ionic conductivity through CL.
[0316] Synthesis of hyperbranched sulfonated phenylated poly(phenylene) (HB-sPPT-H + ) insoluble particles.+ The incorporation of particles into hydrocarbon-based CL and PFSA-based CL does not seem to hinder gas transport and is shown to increase the specific activity of Pt / C catalysts. Figures 9A to 9C As shown, HB-sPPT-H + The use of (5 wt%) can reduce the concentration resistance in PEMFCs, at least in part based on providing a long-range proton conduction path to and from the ultrathin ionomer membrane located near the electrochemical reaction site. When combined with a high-porosity hydrocarbon-based CL, it shows a greater increase in power density for H2 / air operation compared to PFSA-based MEA. Therefore, the impact of hydrocarbon ionomer design in the macropores between catalyst aggregates can be considered.
[0317] Example 2
[0318] Methods and materials for synthesizing polymers and membranes
[0319] The reaction scheme for ionomer synthesis is shown in Fig.10 The materials and methods described herein were used to synthesize linear sulfonated phenylated poly(phenylene) biphenyl (sPPB-H + ) and hyperbranched sulfonated phenylated poly(phenylene) terphenyl (HB-sPPT-H + ) ionomer. Straight chain sPPB-H + The synthesis involves the use of Diels-Alder (DA) polymerization. Perfluorosulfonic acid (PFSA) polymer; NR-211 film (DuPont, TE143904, 25±5 μm thickness) and D520 dispersion (Ion Power Inc., batch number SGA-12-02CS) was used for PFSA-based catalyst coated membranes (CCMs). Pt / C catalyst powder (TEC10E50E, batch number 109-0111, 46.4% Pt) and PTFE treated gas diffusion layers (GDLs) were purchased from FuelCellStore. Methanol (methanol reagent grade ≥99.8%) was purchased from Fischer Scientific.
[0320] 1,3,5-Tris(4-iodophenyl)-benzene(1)
[0321] Iodoacetophenone (15 g, 61 mmol) was reacted neat with p-toluenesulfonic acid (343 mg, 2.03 mmol) and stirred in a pressure vessel at 130 ° C for 5 hours. After completion, the product was dissolved in dichloromethane (20 mL) and precipitated in 95% ethanol. The precipitate was filtered and washed with ethanol to give 1,3,5-tri(4-iodophenyl)benzene as a yellow powder with a yield of 82%.
[0322] 1H NMR (400MHz, CDCl3) δ = 7.84–7.79 (m, 5H), 7.68 (s, 3H), 7.43–7.38 (m, 6H).
[0323] The spectral data are consistent with the literature.
[0324] 1,3,5-Tris(4-trimethylsilylethynylphenyl)benzene(2)
[0325] 1,3,5-tri(4-iodophenyl)benzene (5 g, 7.31 mmol), triphenylphosphine (19 mg, 0.73 mmol), bis(triphenylphosphine)palladium(II)dichloride (46 mg, 0.73 mmol) and trimethylsilylacetylene (3.43 mL, 24 mmol) were dissolved in a mixture of THF (150 mL) and diisopropylamine (25 mL) under an inert atmosphere. Copper(I) iodide (14 mg, 0.73 mmol) was then slowly added to the reaction mixture and stirred at 50 °C for 5 hours. Et2O was poured into the solution and the precipitate was filtered. The filtrate was evaporated, 200 mL of Et2O was added and washed with 1 M hydrochloric acid (200 mL). The organic phase was separated, washed with saturated ammonium chloride solution, water, dried over magnesium sulfate and concentrated in vacuo. The product (92% yield) was collected as a light orange powder and then used without further purification.
[0326] 1 H NMR (400 MHz, acetone) δ = 7.99 (s, 3H), 7.92-7.88 (m, 6H), 7.64-7.57 (m, 6H), 0.26 (s, 27H). The spectral data were consistent with the literature.
[0327] 1,3,5-Tris(4-ethynylphenyl)-benzene(3)
[0328] 1,3,5-tris(4-trimethylsilylethynylphenyl)benzene (2 g, 3.3 mmol) was dissolved in THF (20 mL) and methanol (80 mL). Potassium carbonate (2.79 g, 20 mmol) was added to the reaction and stirred at room temperature for 5 hours and covered with aluminum foil to prevent exposure to sunlight. After completion, 300 mL of dichloromethane was added and the organic phase was washed with water, dried over magnesium sulfate and concentrated in vacuo. The crude product was purified through a silica gel plug with a mixture of hexane / dichloromethane 7:3 to give 1,3,5-tris(4-ethynylphenyl)benzene (460 mg, 73%) as a light yellow powder.
[0329] 1 H NMR (400 MHz, acetone) δ = 8.00 (s, 3H), 7.95–7.87 (m, 6H), 7.67–7.60 (m, 6H), 3.74 (s, 3H). The spectral data were consistent with the literature.
[0330] HB-sPPT-H +
[0331] In a 50mL round-bottom flask, nitrobenzene (14mL) was degassed under argon for 1 hour. TEAsBTC (700mg, 0.497mmol) and 1,3,5-tris(4-ethynylphenyl)benzene (127mg, 0.335 equivalent) were added, the round-bottom flask was covered with aluminum foil and stirred at 170°C for 4 days. The polymer precipitate was washed with ethyl acetate (200mL) to obtain an off-white powder. The polymer was then dispersed in MeOH (100mL) and then exchanged in sodium form by adding 2M NaOH (40mL). The polymer was then filtered as a beige powder and found to be insoluble in MeOH, EtOH, iPrOH, DMAc, DMF, DMSO, NMP and boiling water. The acidification of the polymer was carried out by being dispersed in deionized water (60mL) and 2M HCl (60mL) and filtered to obtain an acidified polymer (503mg), with a yield of 87%.
[0332] Catalyst coated membrane manufacturing
[0333] sPPB-H + Membrane: Acidified polymer sPPB-H + The solid polymer electrolyte (SPE) membrane was cast from DMSO solution (7.5 wt%) at 85 °C. Before the fabrication process, 10 g of sPPB-H + Dissolved in 133g of DMSO and stirred continuously. The resulting polymer solution was vacuum filtered through a glass fiber filter into a round-bottom flask at room temperature. The polymer solution was cast into a film by washing with acid (1M HCl solution), washing with distilled water and placing a MeOH dry grade glass plate on a casting table (K202 controlled coater casting table equipped with a scraper, RK PrintCoat Instrument Ltd). The cast film was peeled off by immersing the glass plate in distilled water. The cast film was removed from the cast film by soaking the cast film in 1M H2SO4 solution for 24 hours, extracting the acidified solution at 8h intervals and replacing 3 times. The film without DMSO was then dried overnight at 80°C under vacuum. These films were then used directly for coating catalysts to make CCM, or dissolved in a solvent (e.g., MeOH) and used to prepare catalyst inks according to the procedures herein. sPPB-H + The membrane exhibited 129 mS cm at 30 °C and 80 °C, respectively, at relatively moderate water content. -1 and 172 mS cm -1 The proton conductivity of sPPB-H produced by the above method is greater than that of NR-211. + The membrane characterization was shown in Figure 2A , 2B , 4A to 4F, 11B to 11F, 12A and 12B.
[0334] Catalyst ink manufacturing
[0335] The following method was used to prepare the catalyst ink, which was used to make the catalyst coated membrane for fuel cell characterization. The data can be found in Figure 2A , 2B , 3A, 3B, 4A to 4F, 5A to 5F. The catalyst coated membrane is composed of the original solid sulfonated phenylated poly (phenylene) biphenyl (sPPB-H + ) polymer electrolyte membrane design and catalyst ink prepared by the following alone or in combination: hyperbranched sulfonated phenylated poly (phenylene) terphenyl (HB-sPPT-H + )、sPPB-H + and D520 ionomer. Linear sPPB-H + and D520 is soluble in alcoholic solvents such as MeOH. + The ionomer is not soluble in MeOH, so a different method is required to prepare its catalyst ink.
[0336] The catalyst ink (1 wt% solids in 1:3 v / v water / methanol) was initially prepared using Pt / C and linear sPPB-H + Ionomer (3 wt% ionomer in MeOH) or A homogeneous solution of D520 was prepared. Initially, one third of the required water was added to the Pt / C solid and the slurry solution was sonicated for 10 min to ensure adequate wetting of the Pt / C particles. The slurry solution was then placed on a stirring plate in a fume hood, one third of the required methanol was added dropwise and stirred for 15 min. The linear sPPB-H + Ionomer or D520 ionomer solution was added, and the ink was stirred for 10 min. The remaining amount of methanol and water were then added dropwise to form a catalyst ink.
[0337] HB-sPPT-H + The ionomer-based catalyst ink was prepared by grinding appropriate solid HB-sPPT-H in the presence of MeOH. + The dried and ground HB-sPPT-H + Ionomers were added to the linear sPPB-H + or The obtained HB-sPPT-H +The catalyst ink was sonicated for 2 hours.
[0338] Catalyst coated membrane
[0339] The catalyst coating membranes used for fuel cell characterization were prepared using the following method, and the data can be found in Figure 2A , 2B , 3A, 3B, 4A to 4F, 5A to 5F, 6, 7A to 7D, 8, 11, 12A and 12B. The hydrocarbon-based electrodes were applied to the original sPPB-H by spraying using a sprayer (Sono-tak ExactaCoat) + The ink was sprayed via an ultrasonic spray forming (accumist) nozzle at 120 kHz and 2 to 6 mm diameter, from left to right and then from bottom to top on a 2D path with a path speed of 75 mm s -1 The reverse process was performed to complete each spray cycle. The shaping air was set to 0.8, the idle and running generator powers were set to 0.5 W and 2 W respectively, and the flow rate was set to 0.3 ml min -1 . Catalyst loading at 5cm 2 The area of (2.24x 2.24cm) was set to 0.4mgPt cm -2 Using the described method, a PFSA-based reference catalyst coated membrane (CCM) was also prepared using D520 dispersion acts as a binder (ionomer) in the catalyst ink and is then applied to The catalyst coated membrane (CCM) was sandwiched between two 7.6 cm 2 The 100 nm PTFE-treated gas diffusion layers (Sigracet 29BC, FuelCellStore) were placed between 100 nm and 200 nm (2.76 x 2.76 cm) of PTFE-treated gas diffusion layers (Sigracet 29BC, FuelCellStore) and compressed into fuel cell hardware (AHNS Co.). Three samples were prepared for each device.
[0340] Electrochemical characterization
[0341] The fuel cell characterization was performed using the following method, and the data can be found in Figure 2A , 2B, 3A, 3B, 4A to 4F, 5A to 5F, 6, 12A, 12B, and 13. A torque wrench was used to compress the MEA between two separate serpentine flow channels in the fuel cell hardware (AHNS Co.). Fuji pre-scaled pressure paper was used to determine whether the compression was sufficient. We tested it on an eight-bolt fixture fuel cell hardware with different applied torque values, ranging from 0.5 to 6.0 Nm, with an increment of 0.5 Nm to ensure equal pressure distribution at the edges. Optimal compression was obtained at 5.7 Nm (50 inch-pounds) using a 130 μm thick glass fiber reinforced PTFE gasket (Hightechflon GbR) and a 50 μm silicone subgasket. The resulting MEA was adjusted using a custom-designed accelerated adjustment program, and the fuel cell operating conditions were set to 80°C and 100% relative humidity (RH); the inlet airflows for the anode and cathode were 0.5 slpm H2 and 1.0 slpm O2, respectively. Before starting the electrochemical characterization, the cell was balanced at open circuit voltage (OCV). Electrochemical characterization was started by running polarization curves, electrochemical impedance spectroscopy (EIS), and cyclic voltammetry (CV) analysis. Tafel analysis was performed on the MEA to determine the Tafel slope and exchange current density. The voltage and current density used for the Tafel plot were corrected for high frequency resistance and H2 cross-polar losses, respectively. 无HFR The mass activity (I m(0.9V) ) and specific activity (I s(0.9V) ). For each electrochemical analysis performed, three samples were tested and the accuracy of each electrochemical analysis performed is indicated by the accompanying standard deviation and appropriate error bars.
[0342] Physical characterization
[0343] Ion exchange capacity (IEC) allows the determination of exchangeable protons in a polymeric material. Before the measurement, the polymer powder was dried under vacuum at 80° C. for 48 hours. IEC measurements were performed in triplicate by immersing the powder in a 1 M NaCl solution for 48 hours and then titrating the solution with 0.01 M NaOH (Sigma Aldrich) using an automatic titrator Metrohm 848 Titrino Plus. The experimental IEC was calculated according to equation (1).
[0344]
[0345] HB-sPPT-H +The water absorption of the powder was measured by a gravimetric method between a wet sample and a dry sample, and repeated three times. Before the water absorption measurement, the sample was dried in a vacuum oven at 80°C for 48 hours and the dry mass of the polymer was measured. The powder was then immersed in deionized water and stirred for 48 hours. The wet polymer was then filtered on a wet glass frit and its wet mass was measured before the end. The water absorption and the number of water molecules per sulfonic acid group were then calculated using equations (2) and (3).
[0346]
[0347] Before DVS measurement, the samples were dried under vacuum at 80° C. The sPPB-H in powder form was measured using a water vapor sorption analyzer (DVS-1000 Adventure) at 80° C. and relative humidity (RH) varied from 0% to 75% in 10% step increments. + and HB-sPPT-H + Isothermal water absorption / loss ( Figure 1D ). Each step was equilibrated for 2 hours.
[0348] The size of insoluble HB-sPPT particles was studied using a Nikon Eclipse 50i equipped with a high-pressure mercury lamp and a Qimaging camera. The resulting image was corrected using a 0.01mm point crosshair ruler for microscope calibration, and the particle size was determined using ImageJ software (developed by the National Institutes of Health). Details of the CL morphology, such as roughness and thickness, were studied using a FEI Nova NanoSEM 430 scanning electron microscope (SEM). For thickness measurement, CCM samples were prepared by freezing each sample in liquid nitrogen and then fracturing it. Samples were typically imaged at an accelerating voltage of 15kV. Images of sample cross sections were taken to determine the thickness of the CL, and high-power images of the sample surface were taken to determine the morphology and roughness of the CCM ( Figure 1B ).
[0349] N2 porosity analysis detailing the pore space within the CL was performed using a Micrometrics ASAP2020 Accelerated Surface Area and Porosimetry System equipped with liquid N2. Ultrapure N2 gas (99.999%) was used in the analysis. Each CCM studied (50 cm 2 ) were fabricated using a previously detailed method using N211 substrates (the measured N2 physisorption was negligible). The Pt loading on both electrodes was 0.4 mg cm -2. The CCM was cut into equal thin strips and degassed at 90°C for 1 hour and then at 105°C for 12 hours. The adsorption and desorption isotherms were measured immediately after degassing and replotted as a function of carbon volume and mass. The Brunauer-Emmett-Teller Surface Area (BET SA) was determined in the range of 0.05 to 0.2 N2 partial pressure. The t-diagram made by plotting the adsorption isotherm against the thickness of the adsorbed layer on the pore wall is used to determine the microporosity within the CL. The thickness t is calculated using the Harkins-Jura equation and the volume of the micropores is estimated from the intercept of the linear region with the y-axis. The above data are shown in Fig. 7E , 7F and 8.
[0350] Example 3
[0351] Improvements in polymer compositions for membranes and catalyst inks
[0352] With straight chain sPPB-H + Different, HB-sPPT-H + The ionomer is insoluble in low boiling protic alcohols, such as MeOH. + -Pt / C catalyst ink is in the form of particles rather than dispersion, indicating that only HB-sPPT-H + The ionomers do not form a bonding network with the Pt / C catalyst. + The resulting CCM made with the -Pt / C catalyst ink showed significant mechanical degradation with large pinholes formed in different parts of the CCM, making it unsuitable for fuel cell operation. + Ionomers were added to HB-sPPT-H in different proportions. + When in an ionomer, a dispersed ink is formed and can bind to the Pt / C on the membrane and thus enable in situ fuel cell characterization.
[0353] To determine the linear sPPB-H + With HB-sPPT-H + Improved combination of ionomers, testing two types of HB-sPPT-H with 15 wt% ionomer content + and linear sPPB-H + Different combinations of ionomers, such as Figures 6A to 6F As shown. Fig.11A From the physical characterization of the CCM obtained in the experiment, it can be observed from the SEM micrograph that the roughness of the CCM surface increases with the increase of HB-sPPT-H + It shows that the content of 5 wt% HB-sPPT-H+ and 10 wt% HB-sPPT-H + The CCMs have the smoothest and roughest CL surfaces, respectively. Figures 11D to 11F The thickness of CCM is shown, where it is noted that the thickness of the anode and cathode catalyst layers increases with the thickness of HB-sPPT-H + The ionomer content increases with the decrease. + At low ionomer content, it was observed that the CL underwent extensive delamination and the CL size was reduced.
[0354] at last, Figures 7A to 7F The polarization curve analysis shown confirmed that 5 wt% HB-sPPT + 10 wt% linear sPPB- + Ionomers are an advantageous combination for achieving improved performance of hydrocarbon-based PEMFCs. Based on CCM, Figures 12A to 12B The polarization curve analysis shown confirms that 5 wt% HB + 25 wt% Ionomers are polymers that have improved properties Advantageous combination of PEMFC.
[0355] Effect of Lower Ionomer Loading
[0356] Figures 4A to 4C and Figures 5A to 5C The in situ electrochemical data shown in Tables 1 to 2 help to understand the + The effect of ionomer on CL was investigated and the reported enhanced performance was not due to a reduction in the linear ionomer content in CL. For hydrocarbon-based CL and PFSA-based CL, the H2 / O2( Figure 4A and Figure 5A ) and H2 / air( Figure 4B and Figure 4B ) under the polarization and power curves, the extracted data are listed in Tables 1 to 2. It shows that for hydrocarbon CCM, under H2 / O2 (H2 / air) operation, 5 wt% HB-sPPT-H + +10 wt% sPPB-H + The peak power density is higher than that of CL containing 10 wt% sPPB-H + The CCM of the ionomer is 67% higher (53%). Similarly, for the PFSA CCM, under H2 / O2 (H2 / air) operation, 5 wt% HB-sPPT-H + +25% by weight The peak power density is higher than that of The CL of the ionomer is 10% (18%) higher. Thus, from the data shown for I to V, it is noted that although the particle size is assumed to be Figures 11D to 11FThe catalyst layer thickness shown is of the same order of magnitude, but HB-sPPT-H + Plays a positive role in PEMFC performance.
[0357] Similarly, from the mass activity (I m(0.9V) ) and specific activity (I s(0.9V) ) are extracted from the values shown in Tables 1 to 2. Fig. 12A (hydrocarbons) and Fig. 12B (PFSA) shows that it should be noted that HB-sPPT-H + The presence of ionomers increases the traditionally low mass activity and specific activity of hydrocarbon-based CCMs by >80%. Based on CCM, when CL contains 5 wt% HB-sPPT-H + When the ionomer is used, the reported specific activity increases by more than 40%. This is comparable to the + +10 wt% HB-sPPB-H + Ionomer (839mΩcm 2 )'s charge transfer resistance R at 0.8V ct(0.8V) The charge transfer resistance is consistent with that of 15 wt% sPPB-H. + Ionomer (885mΩcm 2 ) and CCM with only 10 wt% sPPT-H+ ionomer (1297 mΩcm 2 ) is better, such as Figure 4D It is observed that with 30 wt% and 25 wt% Compared with the two CCMs of ionomer, R ct(0.8V) There is a similar trend with 5 wt% HB-sPPT-H + +25% by weight of Base CCM( Figure 5D ) showed the lowest charge transfer resistance.
[0358] like Figure 4E and Figure 5E As shown, CCMs with lower linear ionomer content, that is, 10 wt% HB-sPPB- + CCM( Figure 4E ) and having 25 wt % CCM( Figure 5E ) reported lower ECSA values. The lower reported ECSA values are likely due to the more discontinuous proton conduction pathways associated with subcritical ionomer content. These conclusions are supported by EIS measurements in H2 / N2 environments ( Figure 4F and 5F), where the reduced ionomer content resulted in low ionic conductivity of the catalyst layer (15 wt % HB-sPPB-H + R ionic-CL =598mΩcm 2 and 10 wt% HB-sPPB-H + R ionic-CL =1421mΩcm 2 ), as shown in Tables 1 to 2. + The CCM has significantly lower weight than 15 wt% HB-sPPB-H + and 10 wt% HB-sPPB-H + R of the base CCM (8 and 20 times lower, respectively) ionic-CL , which indicates that due to the HB-sPPT-H + Ionomers lead to higher proton conductivity. Base CCM, HB-sPPT-H + The existence of However, the enhancement is smaller than that observed for hydrocarbon-based CCMs, but is likely due to Ionomers are able to form coordinated networks, the The CCM-based materials generally exhibit higher ionic conductivity.
[0359] Example 4
[0360] Uses of Hyperbranched Ionomers
[0361] Hyperbranched ionomers are used in combination with a third type of ionomer commonly used in catalyst layers and other commercial proton exchange membranes.
[0362] Experiments were performed as described herein and performance graphs of the MEA were generated, which show a Pt catalyst loading of 0.4 mg Pt / cm on the anode and cathode under H2 / O2. 2 , and the operating conditions are 80°C, 100% RH and 1atm pressure ( Fig.13A ) and the Pt catalyst loading on the anode and cathode is 0.4 mg Pt / cm2 under H2 / air operation. 2 The operating conditions are 80°C, 100% RH and 1 atm pressure ( Fig. 13B )’s polarization and power curves. Fig.13A and 13B The data in this article are obtained from the PF1-HLF8-15-X The membrane and the catalyst layer including 15 wt% PP1-HNN8-00-X, as shown in the circled data; obtained from the catalyst layer including PF1-HLF8-15-X A membrane, and a catalyst layer comprising 4.1 wt% HB-sPPT + 8.4 wt% PP1-HNN8-00-X ionomer, as shown in the data represented by the pentagons; and obtained from DuPont N211 film, and comprising 30 wt% of DuPont The catalyst layer of D520 is shown in the hexagonal data. The peak power density and the power density at 0.6 V are shown in Table 6.
[0363] The results demonstrate state-of-the-art performance for hydrogen PEM fuel cells operating under ambient conditions (air or oxygen).
[0364] Table 6: Peak power density and power density at 0.6 V for PEM fuel cell operation of ionomers used in combination with the third type of ionomer.
[0365]
Claims
1. A branched or hyperbranched ionomer polymer comprising repeating units of formula (I): comprising anionic comonomers and branched comonomers (B), in: R 1A , R 1B , R 1C , R 1D , R 1E and R 1F are independently aryl or heteroaryl, each of which is optionally substituted with 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cation, and the limiting condition is R 1A , R 1B , R 1C , R 1D , R 1E and R 1F At least two of them are independently selected from SO3 by 1, 2, 3, 4 or 5 independently selected - X + PO3 2- X + 2 and COO - X + A substituent substituted aryl or heteroaryl, wherein X + Yes H + or cations; R 1G and R 1H are independently H, aryl or heteroaryl, wherein the aryl and heteroaryl are each optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cations; A1 is arylene, heteroarylene, aralkylene or heteroaralkylene, each of which is optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl; and A2 is absent, arylene or heteroarylene, wherein said arylene and heteroarylene are each optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl; B is a branched comonomer; R 2A is a key; and The first repeating unit of formula (I) is 2A The second repeating unit of formula (I) is combined to form a branched structure.
2. The branched or hyperbranched ionomer polymer according to any one of the preceding claims, wherein the polymer is insoluble in polar solvents.
3. The branched or hyperbranched ionomer polymer according to any one of the preceding claims, wherein the molar ratio of Z:Y in the polymer is from 1:3 to 1:
2.
4. The branched or hyperbranched ionomer polymer according to any one of the preceding claims, wherein the branched comonomer (B) comprises a structure of formula (II): in: L3 is, at each occurrence, an optionally substituted polyvalent heteroatom (e.g., N, P, B), polyvalent aryl, polyvalent heteroaryl, polyvalent aralkyl, or polyvalent heteroaralkyl, wherein the polyvalent aryl, polyvalent heteroaryl, polyvalent aralkyl, and polyvalent heteroaralkyl are each optionally substituted with 1, 2, or 3 residues independently selected from C 1-6 Substitution of alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; L2 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 Alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; and L1 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 Substituents of alkyl, halo, nitro, cyano, aryl and heteroaryl groups are substituted.
5. The branched or hyperbranched ionomer polymer according to any one of the preceding claims, wherein the branched comonomer (B) comprises a structure of formula (III):
6. The branched or hyperbranched ionomer polymer according to any one of the preceding claims, wherein the anionic comonomer comprises a structure of formula (VII):
7. The branched or hyperbranched ionomer polymer according to any one of the preceding claims, wherein the repeating unit comprises a structure of formula (IV):
8. The branched or hyperbranched ionomer polymer according to any one of the preceding claims, wherein the branched or hyperbranched ionomer polymer is formed by polymerization of a functionalized branched comonomer (B) and a functionalized anionic comonomer, wherein the molar ratio of the functionalized branched comonomer (B) to the functionalized anionic comonomer is greater than 0.
2.
9. The polymer of claim 8, wherein the molar ratio of the functionalized branched comonomer (B) to the functionalized anionic comonomer is about 0.
667.
10. The branched or hyperbranched ionomeric polymer according to any one of the preceding claims, further comprising a difunctional monomer C.
11. A catalyst ink formulation comprising: A branched or hyperbranched ionomer polymer having the structure according to claims 1 to 10; linear ionomer polymers; Polar solvents; and catalyst, The linear ionomer polymer is dispersed in the polar solvent, and the amount of the linear ionomer polymer used is such that the branched or hyperbranched ionomer polymer can be dispersed in the polar solvent.
12. The catalyst ink formulation of claim 11, wherein the polar solvent comprises an alcohol having a boiling point of less than 120°C.
13. The catalyst ink formulation according to any one of claims 11-12, wherein the alcohol is methanol.
14. The catalyst ink formulation of any one of claims 11 to 13, wherein the polar solvent further comprises water, and wherein the volume to volume ratio amount of water to alcohol is from about 1:3 to about 3:
1.
15. The catalyst ink formulation of any one of claims 11 to 14, wherein the branched or hyperbranched ionomer polymer is present in the formulation in an amount from about 0.01 wt% to about 10 wt% of the total solids content.
16. The catalyst ink formulation according to any one of claims 11 to 15, wherein the linear ionomer polymer is a linear sulfonated phenylated poly(phenylene) biphenyl (sPPB-H + ) ionomers, including sPPB-H + and a random copolymer of hydrophobic units, a PFSA material, or a combination thereof.
17. The catalyst ink formulation of any one of claims 11 to 16, wherein the amount of the linear ionomer polymer is about equal to or greater than the amount of the branched or hyperbranched ionomer polymer.
18. The catalyst ink formulation of any one of claims 11 to 17, wherein the formulation comprises an amount of branched or hyperbranched ionomer polymer and an amount of linear ionomer polymer, wherein the total amount of the branched, hyperbranched and linear ionomer polymers dispersed in the polar solvent is from about 0.1% w / v to about 25% w / v.
19. The catalyst ink formulation according to any one of claims 11 to 18, wherein the catalyst is Pt / C, PtCo / C, MNC catalyst or a combination thereof.
20. The catalyst ink formulation of any one of claims 11 to 19, comprising the catalyst in an amount between about 0.1% w / v to about 25% w / v.
21. An ionomer polymer membrane comprising: Mechanical reinforcements; and An ionomeric binder coupled to the mechanical reinforcement, wherein the ionomeric binder comprises a linear ionomeric polymer, a branched ionomeric polymer, a hyperbranched ionomeric polymer, or a combination thereof according to any one of claims 1 to 10.
22. A catalyst-coated ionomer polymer membrane comprising: The ionomer polymer membrane according to claim 21; and A catalyst layer is in contact with the ionomer polymer membrane.
23. The catalyst coated ionomer polymer membrane of claim 22, wherein the catalyst layer is formed from a catalyst ink, and wherein the catalyst ink is a catalyst ink formulation according to any one of claims 11 to 20.
24. The catalyst coated ionomer polymer membrane of any one of claims 22-23, wherein the catalyst layer comprises Pt / C, PtCo / C, MNC catalyst, or a combination thereof.
25. The catalyst coated ionomer polymer membrane of any one of claims 22 to 24, wherein the ionomer polymer membrane has a top surface and a bottom surface, and wherein the catalyst layer is in contact with only the ionomer polymer top surface, only the ionomer polymer bottom surface, or both the ionomer polymer top and bottom surfaces, wherein a bilayer is formed when the catalyst layer is in contact with only the top surface or only the bottom surface of the ionomer polymer membrane, and Wherein when the catalyst layer contacts both the top surface and the bottom surface of the ionomer polymer membrane, three layers are formed.
26. The catalyst-coated ionomer polymer membrane according to any one of claims 22 to 25, wherein the catalyst layer of the top surface of the ionomer polymer membrane and the catalyst layer of the bottom surface of the ionomer polymer membrane are anodes or cathodes, wherein when only one surface of the ionomer polymer is in contact with the catalyst layer, the catalyst layer is an anode or a cathode, and Wherein when both surfaces of the ionomer polymer are in contact with the catalyst layers, one catalyst layer is an anode and the other catalyst layer is a cathode.
27. The ionomeric polymer membrane of claim 21 or the catalyst coated ionomeric polymer membrane of any one of claims 22 to 26, wherein the mechanical reinforcement comprises a porous polymeric material.
28. The ionomer polymer membrane of claim 21 or the catalyst coated ionomer polymer membrane of any one of claims 22 to 27, wherein the linear ionomer polymer of the ionomer binder is a linear sulfonated phenylated poly(phenylene) biphenyl (sPPB-H + ) ionomers, including sPPB-H + and a random copolymer of hydrophobic units, a PFSA material, or a combination thereof.
29. The catalyst-coated ionomer polymer membrane of any one of claims 22-28, wherein the catalyst layer comprises an ionomer polymer, and wherein the ionomer polymer comprises a linear ionomer polymer, a branched ionomer polymer, a hyperbranched ionomer polymer, or a combination thereof of any one of claims 1-10.
30. The catalyst coated ionomer polymer membrane of any one of claims 22 to 29, wherein: The branched or hyperbranched ionomer polymer of the catalyst layer is present in an amount from about 0.5 wt % to about 25 wt % of the weight of the catalyst layer; and The linear ionomeric polymer of the catalyst layer is present in an amount about equal to or greater than the amount of the branched or hyperbranched ionomeric polymer of the catalyst layer.
31. The ionomeric polymer membrane of claim 21 or the catalyst coated ionomeric polymer membrane of any one of claims 22 to 30, wherein the mechanical reinforcement, the ionomeric binder and the catalyst layer are substantially free of halogen.
32. A method for synthesizing a branched or hyperbranched ionomer polymer, the method comprising: The Diels-Alder addition reaction was used to m The molar ratio of the functionalized branched comonomer (B) to Y m moles of functionalized anionic comonomers polymerized, in: The functionalized branched comonomer (B) is a dienophile; The functionalized anionic comonomer is a diene; and Z m :Y m The molar ratio is greater than 0.
2.
33. The method of claim 32, wherein Z m :Y m The molar ratio is about 0.
67.
34. The method of any one of claims 32 to 33, wherein the functionalized branched comonomer (B) has a structure according to formula (V): in: L3 is, at each occurrence, an optionally substituted polyvalent heteroatom (e.g., N, P, B), polyvalent aryl, polyvalent heteroaryl, polyvalent aralkyl, or polyvalent heteroaralkyl, wherein the polyvalent aryl, polyvalent heteroaryl, polyvalent aralkyl, and polyvalent heteroaralkyl are each optionally substituted with 1, 2, or 3 residues independently selected from C 1-6 Substitution of alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; L2 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; L1 is absent, arylene or heteroarylene, wherein the arylene and heteroarylene are each optionally substituted by 1, 2, 3 or 4 independently selected from C 1-6 Alkyl, halo, nitro, cyano, aryl and heteroaryl substituents; and D1, D2 and D3 are independently H, R 1G , R 1H , R 3G , R 3H or a protecting group (e.g., a silyl protecting group, a substituted silyl protecting group, a trialkylsilyl protecting group, a silyl ether protecting group, a trialkylsilyl ether protecting group, or a trimethylsilyl ether), Where R 1G and R 1H is independently H, aryl or heteroaryl, wherein the aryl and heteroaryl are each optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, nitro, cyano, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cations; and Where R 3G and R 3H are independently alkyl, aryl or aralkyl.
35. The method of any one of claims 32 to 34, wherein the functionalized branched comonomer (B) has a structure according to formula (VIII):
36. The method of any one of claims 32 to 35, wherein the functionalized anionic comonomer has a structure according to formula (VI): in: R 1A , R 1B , R 1C , R 1D , R 1E and R 1F is independently aryl or heteroaryl, each of which is optionally substituted by 1, 2, 3, 4 or 5 independently selected from C 1-6 Alkyl, halogen, SO3 - X + PO3 2- X + 2 and COO - X + Substituents, where X + Yes H + or cation, and the limiting condition is R 1A , R 1B , R 1C , R 1D , R 1E and R 1F At least two of them are independently selected from SO3 by 1, 2, 3, 4 or 5 independently selected - X + PO3 2- X + 2 and COO - X + A substituent substituted aryl or heteroaryl, wherein X + Yes H + or cations; A1 is arylene, heteroarylene, aralkylene or heteroaralkylene, each of which is optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl; and A2 is absent, arylene or heteroarylene, wherein said arylene and heteroarylene are each optionally substituted with 1, 2, 3 or 4 substituents independently selected from halo, nitro, cyano, aryl and heteroaryl.
37. The method of any one of claims 32 to 36, wherein the functionalized anionic comonomer is:
